Metabolomics-based analysis of dynamic metabolic trajectories and regulatory networks in two-stage fermentation of kiwifruit wine - Wangsheng Sun; Pengfei Bi; Wanju Yan; Rou Cai; Zhendong Zhang; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Jing Guo (Food Microbiology, 2027)

Spatially dispersed hydrophobic SiO2 on HZSM-5 zeolite for catalytic upgrading of Bio-oil - Penglong Jia; Rui Yang; Pattreeya Panpian; Zhihua Zhang; Lianfeng Zhu; Yushani Alahakoon; Wei Huang; Jing Wang; Abuliti Abudula; Ye Shui Zhang; Guoqing Guan (Fuel, 2026)

Quality formation mechanism of shiitake mushrooms during multiphase microwave drying (MMD) - Zhenbin Liu; Jia Luo; Jiayi Zhang; Rui Weng; Wenchao Liu; Hongbo Li; Huan Cheng; Dong Wang; Hengchao E; Lu Tian; Haizhen Mo; Liangbin Hu (Food Control, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Level terraces enhance the vertical distribution of soil organic carbon in mixed forests: microbial mechanisms and carbon fraction dynamics on the loess plateau - Zhe Li; Ning Zhang; Zi-ming Wang; Rui-kun Feng; Yi-qiao Chen; Zheng-hua Liu; Wen-fan Wang; Jia-bin Liu; Jian Wang (CATENA, 2026)

Oxalate-assisted formation mechanism of lignocellulose-based two-dimensional porous carbon and its application in zinc-ion hybrid capacitors - Xiaotong Ma; Xiaohao Liu; Lijie Sun; Rui Diao; Dongxu Yan; Zhenting Zha; Liangyuan Jia; Fenglei Qi; Zhitao Zhang; Yingcui Fang; Peiyong Ma (Bioresource Technology, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Concept design, simulation and image reconstruction of gamma-ray emission computed tomography (GECT) for non-destructive inspection of nuclear fuel assemblies - Zhanfei Liu; Jingru Chen; Mingfei Yan; Xubin Zhang; Lucheng Yang; Wenxuan Zhang; Rui Jia; Huasi Hu (Annals of Nuclear Energy, 2026)

Microplastics induce PSTs synthesis in Alexandrium tamarense and their combined toxicity to juvenile Mytilus galloprovincialis - Ying Zhang; Chuner Cai; Rui Jia (Marine Pollution Bulletin, 2026)

Photodegradation remodels plastic carbon pool: Unveiling transformation and fate of particulate, dissolved and gaseous carbon fractions - Taishuo Zhang; Rui Wang; Jian Wang; Zhengyang Shang; Jiarui Zhao; Xiaoqian Ye; Zixuan Zhang; Xinrui Zhang; Haiyu Zhang; Ziyan Li; Peng Liu; Hanzhong Jia (Water Research, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Balancing fermentation control and aroma complexity in semi-spontaneous kiwifruit fermentation through Saccharomyces cerevisiae inoculum level - Wanju Yan; Yuanjing Li; Zitong Zhang; Rou Cai; Sinuo Feng; Jia Han; Wangsheng Sun; Rui Cai; Zhouli Wang; Jing Guo (Food Research International, 2026)

Biochar strengthens rainfall regime resistance of soil inorganic C by enhancing pH–bicarbonate and carbonic anhydrase regulation in dryland region - Yuhao Wang; Yanbo Ji; Shutong Guo; Lin Sun; Enke Liu; Zhikuan Jia; Kadambot H.M. Siddique; Rui Qian; Ting Wei; Peng Zhang (Agriculture, Ecosystems & Environment, 2026)

Enhancing resistance against white spot syndrome virus in Litopenaeus vannamei via recombinant Lactobacillus acidophilus through modulation of gut microbiota function - Hang Zhang; Wei Liu; Yi-Ning Cui; Pei-Min He; Ji-shun Yang; Rui Jia (Aquaculture, 2026)

Discovery of swertimusins A‒D: Four pairs of rearranged nor-secoiridoid derivatives with a hexahydrofuro[2,3-b]furan ring from Swertia mussotii - Xue Cheng; Qi-Feng Zhang; Rui-Kang Tan; Wen-Di Wang; Yu-Rui Dou; Jia-Yi Wei; Ke-Xun She; Xiao-Feng He (Phytochemistry, 2026)

Effect of double-cropping pattern on biological yield and quality of silage corn across different cropping systems in the Hebei region - Liang Song; Min Jia; Quanguo Zhang; Jianghao Wang; Liwei Wang; Rui Guo; Yuanyuan Yan; Jianfeng Wei; Xinghua Li; Wei Song (Next Research, 2026)

Transient geomorphic processes revealed by luminescence sensitivity of Yellow River terrace sediments - Ya Liu; Zheng-Hao Gu; Jia-Fu Zhang; Xue Rui; Yu-Jie Guo; Song-Xi Du; Yu-He Shen; Qing-Hao Ma (Geomorphology, 2026)

Decoding lipid signatures and aroma characteristics of four Chinese traditional dark teas via integrative lipidomics, volatilomics, and quantitative descriptive analysis - Shan Zhang; Ruizhi Tang; Yunxia Wang; Ying Wang; Chuang Zhou; Rui Shen; Rui Liang; Niuniu Mao; Yinzi Chen; Nan Deng; Qinghua Zhou; Jia Li; et al. (Food Research International, 2026)

Multi-omics combined with simulated fermentation model for elucidation of variation patterns of lipids and volatiles and its mechanism during black tea fermentation - Linchi Niu; Yuning Feng; Shan Zhang; Zhizhen Fang; Rui Liang; Zhenxing Xu; Xujiang Shan; Qinghua Zhou; Haibo Yuan; Yongwen Jiang; Jia Li (Food Chemistry, 2026)

Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Enhanced degradation of sulfamethoxazole in dielectric barrier discharge plasma via Zn tetrahedral site doping-mediated d-band center engineering of CoFe2O4 - Xiaojing Wang; Rui Cao; Na Huang; Mengmeng Du; Mingyao Yuan; Jia Ma; Fan Zhang; Jiaqi Jiang; Zhenxing Zeng; Yanzong Zhang; Zhilin Li; Shihuai Deng (Chemical Engineering Journal, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Breaking the “Wall”: Mechanistic insights into low-intensity ultrasound (LIU)-induced recovery of calcified CANDAN granular sludge - Shenbin Cao; Yucheng Tao; Meng Zhang; Mingsheng Jia; Xiaoyan Fan; Rui Du; Yongzhen Peng (Water Research, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Tailoring polyhydroxybutyrate by molecular weight regulation: Green synthesis, food-grade performance and innovative ketogenic applications - Jin Hui Xie; Jia Ying Xin; Yan Wang; Li Rui Sun; Hai Xin Bi; Jian Xiong Zhang; Chun Gu Xia (Food Research International, 2026)

Two-phase flow in clayey silt hydrate reservoirs drives migration and clogging of fine clay particles - Jiang Lei; Wei Guo; Yuan Wang; Wen Zhang; Huie Chen; Pengyu Zhang; Rui Jia (Engineering Geology, 2026)

Relative-effect metrics do not reflect societal burden under population ageing: Evidence from cold spell–related dementia mortality in China - Rui Zhang; Songwang Wang; Yujie Meng; Huan Zheng; Zixiong Zhao; Qing Guo; Shuo Zhan; Qiang Chen; Chaonan Wang; Jia Zhao; Ainan Jia; Xuejie Du; et al. (Environmental Impact Assessment Review, 2026)

Autophagy-augmenting peptide nanoplatform for synergistic chemo-immunotherapy against breast cancer - Chen Wei; Wei Gao; Xingyue Li; Ming Fu; Fantao Lin; Xiaoyu Zhao; Huiying Jia; Kang Zhang; Changgang Sun; Rui Wang; Jingkun Bai (Chemical Engineering Journal, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Astronomically forced climate change during the Middle Oligocene-Early Miocene in the Pearl River Mouth Basin, Northern South China Sea - Shizhen Jia; Yanzhen Li; Mengqing Shang; Rui Liu; Linzhen Hu; Yongming Zhang; Xiuju Xing; Zi’ang Yang (Marine Geophysical Research, 2026)

Effect of the thickness of overlying soil on the location of trailing edge cracks in soil–bedrock landslides induced by water softening - Yun-kang Rao; Jia-xin Chang; Hai-ying Fu; Tao Yang; Huai-lin Chen; Zhe Zhang; Yi Yang; Rui Huang (Bulletin of Engineering Geology and the Environment, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

A novel AGTPBP1-ERK/MYLK network mediates pancreatic cancer progression - Zhe-yu Yang; Qian Zhang; Jing-rui Yang; Xiao-dong Zhang; Chang-le Liu; Jia-yu Huang; Rui Xiao; Jian-jun Ren (Tissue and Cell, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Divergent microplastic assemblages across natural and artificial waters in the Wei River Basin - Yiping Guo; Zhe Liu; Houpu Ren; Zixuan Zhang; Shichen Wei; Guojin Qi; Taishuo Zhang; Rui Wang; Xinyu Xu; Peng Liu; Hanzhong Jia (Journal of Water Process Engineering, 2026)

Enhanced water level fluctuations reduced the competitive advantage of cyanobacteria - Yan Chen; Rui Xia; Ruining Jia; Junde Ming; Kai Zhang; Jinghui Dou; Tianxiang Zhao; Xiang Li; Qin Zhang; Qi Zhang (Journal of Hydrology, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Speleothem multi-proxy inferred hydroclimate variability during the 2.8 ka event and its influence on human activities in southeastern China - Xiaomei Zhang; Haiwei Zhang; Ashish Sinha; Miaomiao Wang; Jian Wang; Yueer Li; Liangkang Pan; Rui Zhang; Youfeng Ning; Xuexue Jia; Baoyun Zong; Hai Cheng (Global and Planetary Change, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Differential volatile-omics analysis for tamarind (Tamarindus indica L.) and aroma-active compounds identification via DMU-SPME-GC-MS method - Rui-Hua Jin; Ling Zhang; Li-Bo Qi; Chun-Mei Yuan; Zi-Bo Song; Jia-Teng Chen; Ming Du; Xian-Bing Xu (Food Chemistry, 2026)

Cobalt Sites as Electron Transfer Hubs in Medium-entropy FeCoMnZnCu@NC: Driving Multi-site Cooperation for Efficient Singlet Oxygen Generation - Jia Ma; Mingyao Yuan; Rui Cao; Na Huang; Zhenxing Zeng; Yanzong Zhang; Shihuai Deng; Xiaojing Wang (Water, Air, & Soil Pollution, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Effect of first-stage anode axial position on discharge characteristics of a double-stage anode layer thruster - Rui Ding; Sheng Wen; Zhihao Liu; Jia Liu; Guanrong Hang; Yan Zhang; Ximing Zhu; Yongjie Ding (Advances in Space Research, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Tuning the fate of radical intermediates: The pivotal role of catalyst acidity and texture in steering lignin pyrolysis pathways - Yuyang Fan; Chao Liu; Zhengxue Zhang; Shiliang Wu; Anqing Zheng; Zhaojuan Zheng; Jia Ouyang; Rui Xiao (Fuel, 2026)

Visible-light-driven N-CDs/Cu photocatalysis for CO2 valorization to selenylated vinyl oxazolidinones - Jun-Bo Wang; Jia-Tong Guo; Shu-Rui Wang; Bei Ruan; Zhan-Hui Zhang (Chemical Engineering Journal, 2026)

Rhizosphere microbiome and soil health effects on ginseng growth performance and ginsenoside accumulation - Jing Fang; Rui Liu; Kemeng Zhang; Yingmei Sun; Yan Xue; Changbao Chen; Tao Zhang; Qinghe Zhang; Jia Chen (Plant and Soil, 2026)

Cross-instrument coal quality spectral analysis via a PDS-assisted fine-tuning calibration transfer method - Junlong Gao; Jiaxuan Li; Jiaxin Yin; Rui Gao; Zhihui Tian; Yang Zhao; Yu Bai; Lei Dong; Weiguang Ma; Lei Zhang; Wangbao Yin; Suoteng Jia (Analytica Chimica Acta, 2026)

Adaptive Fixed-Time Control Framework for Deterministic Response of Fully Constrained Vessels with Unknown Dynamics - Qiang Guo; Shuangpeng Duan; Jia Zhou; Shengguo Wang; Rui Li; Xianku Zhang (Journal of Marine Science and Engineering, 2026)
To achieve precise trajectory tracking for surface vessels subject to unknown dynamics, strict physical limitations, and external disturbances, this paper proposes an Adaptive Fixed-Time Control Framework that ensures a deterministic response under full constraints. First, navigation safety is guaranteed by employing a Barrier Lyapunov Function (BLF) to strictly confine vessel position states, enabling constrained position tracking without requiring prior knowledge of the desired trajectory. Second, addressing the input constraint aspect of the “full constraints” problem, a fixed-time auxiliary system is introduced to compensate for nonlinearities induced by actuator saturation, thereby maintaining control feasibility. Central to this framework is the realization of a deterministic response; by incorporating fixed-time convergence theory, the controller guarantees that velocity tracking errors converge within a predefined time bound independent of initial conditions. Furthermore, an RBF neural network combined with adaptive techniques is utilized to estimate unknown dynamics and external disturbance bounds online, enhancing robustness and safety in realistic marine environments.

Fe-N-C-supported LaFeO3 heterojunction electrodes for efficient copper and fluoride removal in symmetric capacitive deionization - Shaojian Xie; Yujia Wang; Rui Zhang; Lei Huang; Jia Yan; Zhenxin Chen; Hongguo Zhang; Meng Li; Hongbo Zeng (Water Research, 2026)

Performance enhancement of cryogenic nitrogen ejectors for HEPS: a model-data dual-driven approach - Yu-Qing Wang; Ran Ding; Jia-Rong Zhang; Rui Ge; Chang-Cheng Ma; Yi Huo (International Journal of Refrigeration, 2026)

Antimony precipitation processes of orogenic and magmatic-hydrothermal gold‑antimony systems in the West Qinling Orogen, China - Lian Zhang; Hao-Cheng Yu; Jie Wang; Rui Zhu; Lei Wang; Deng-Yang He; Jin-Hong Qiu; Jia-Hui Zhou; Kun-Feng Qiu (Chemical Geology, 2026)

Does a positive culture correlate with the volume of synovial fluid inoculated into blood culture bottles for the diagnosis of periprosthetic joint infection? - Jia-Zheng Xu; Zhi-Sen Gao; Zhen Zhang; Ping Song; Wei Chai; Rui Li (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Mobilization of cadmium and lead mediated by iron and manganese reduction in coastal wetlands of Yueqing Bay, China - Qing-Rui Jiang; Jia-Xi Pang; Wei-Wei Ma; Wen-Zhuo Zhu; Jian Wang; Xiao-Ping Chai; Lu-Ping Song; Yi-Ying Zhang; Jian-Xin Wang (Marine Pollution Bulletin, 2026)

Corrigendum to “Flow backward alleviated the river algal blooms” [Volume 245, 15 October 2023, 120593] - Yan Chen; Rui Xia; Ruining Jia; Qiang Hu; Zhongwen Yang; Lu Wang; Kai Zhang; Yao Wang; Xiaojiao Zhang (Water Research, 2026)

Remote sensing-based estimation of global litterfall dynamics in forest ecosystems and its potential impact on soil respiration - Chunsheng Wang; Qingjiu Tian; Wenmin Zhang; Lili Chang; Jia Tian; Rui Zhang (Remote Sensing of Environment, 2026)

Machine-learning-guided risk stratification of bacterial contamination in food powered by a dual-mode lateral flow biosensor using low-crystallinity nanozyme labels - Rui Shu; Sijie Liu; Huilin Jia; Lei zhao; Ibrahim A. Darwish; Jianlong Wang; Daohong Zhang (Food Research International, 2026)

Bioactive edestin peptides from hemp (Cannabis sativa L.) seeds improve exercise performance under hypobaric hypoxia - Rui Zhang; Jie Liu; Liang-Liang Chen; Jia-Qi Liu; Xiao-Qian Jin; Zi-Xian Fu; Jun-Bin Xiong; Bin Jia; Jun-Ling Shi; Da-Chuan Yin (Food Research International, 2026)

Strain-specific effects of infant-derived Bifidobacterium on gut microbiota modulation and mucus barrier responses in Salmonella infection - Xiaogan Zhao; Mahsa Ghahvechi Chaeipeima; Luyao Xiao; Xia Fan; Wenkai Jiang; Xiran Jia; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Bioscience, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Nitrogen fertilization shapes rhizosphere microbiome to boost peanut yield: A two-year field study - Xiangjun Kong; Peipei Jia; Lijie Li; Ali Muhammad; Rui Wang; Aziz Khan; Jaya Nepal; Fei Li; Zhiyong Zhang (Applied Soil Ecology, 2026)

Corrigendum to “Targeting YBX1: A novel therapeutic strategy for gastric cancer through regulation of cellular senescence and mTOR signaling” [Tissue and Cell, 97 (2025) 103089] - Wenze Zhang; Yanjuan Jia; Anqi Wang; Rui Guo; Zhuomin Fu; Wanxia Wang (Tissue and Cell, 2026)

Editor's note “Phosphorus – the main limiting factor in riverine ecosystems in China” [Sci. Total Environ. 870 (2023) 161613] - Yan Chen; Jie Chen; Rui Xia; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2026)

Immobilized Pseudomonas sp. DNB-S1 on modified biochar enables synergistic DBP remediation and soil health enhancement - Rui Guan; Lei Wang; Jian Guan; Jianan Liu; Ying Zhang; Xiaochen Jia; Yarui Xin (Journal of Environmental Chemical Engineering, 2026)

Fabrication of novel FO membrane supported on PU-PAN electrospun nanofiber membrane for high-permeability and selectivity - Dibakar Pandaya; Yu-Qian Yue; Zhen-Liang Xu; Ming-Xiao Zhang; Rui Jia; Mateen Hedar; Muhammad Irfan; Liang Cheng; Yong-Jian Tang; Mahesh Kumar Joshi (Journal of Environmental Chemical Engineering, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Surface aging of Ti-based MXene attenuates mitochondrial toxicity via suppressed cellular uptake and reactivity - Rui Zhang; Xiaodi Li; Yujiao Liu; Xuan Mao; Yongyi Wei; Yu Wang; Xiaofei Zhou; Jianbo Jia (Environmental Pollution, 2026)

Complete upcycling of iron phosphate slag via ammonium sulfide: Synchronous recovery of phosphorus, Fe7S8/C catalyst, and elemental sulfur - Shaoxiang Yang; Fei Zhang; Yikun Li; Fang Wang; Jiayu Feng; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Lijuan Jia (Chemical Engineering Journal, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Advancement and field evaluation of a honeysuckle harvesting robot with integrated clamping and air-suction mechanisms - Zhaoyu Rui; Zhao Zhang; Cunming Hao; Yingxin Jia; Zhenhuan Ye; Saddam Hussain; Mahmoud A. Abdelhamid; C. Igathinathane; Yiannis Ampatzidis (Computers and Electronics in Agriculture, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

Revealing the key role of Pt and Pd sites in the promotion or inhibition of H2O on CO catalytic oxidation - Ning Hou; Cangpeng Shan; Xiaohua Zhu; Hui Wang; Wenbo Zhang; Qinwei Jia; Yufan Jiang; Rui Han; Qingling Liu (Fuel, 2026)

Construction and textural modification of soft surimi gel from spanish mackerel (Scomberomorus niphonius) by polysaccharides - Yin-Yin Lv; Xian-Hao Zhang; Jia-Ni Zhou; Ying-Rui Wang; Zhu-Jun Zhang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

An ANN-based framework for mapping urban tree cooling and exposure inequality in a high-density city: A case study of Hong Kong - Siqi Jia; Di Wei; Rui Zhang; Fanhua Kong; Yuhong Wang (Urban Forestry & Urban Greening, 2026)

Wave-absorbing grouting for mitigating rockbursts triggered by multi dynamic disturbances in deep tunnels - Heng-Yuan Zhang; Ben-Guo He; Xiang-Rui Meng; Jia-Hua Guan; Hua-Wei Xu (Tunnelling and Underground Space Technology, 2026)

Soil organic matter revisited: Why humic substances still matter? - Sen DOU; Yifeng ZHANG; Jun SHAN; Meng WU; Rui MA; Song GUAN; Zhongjun JIA (Pedosphere, 2026)

Study on the irradiation control of urease activity and its solidification of red clay to enhance radon reduction - Yuanyuan Tang; Rui Liang; Jia Wei; Yiqing Sun; Weihang Peng; Fubing Li; Chengyu Zhang; Changshou Hong (Journal of Environmental Radioactivity, 2026)

Grain-size controls on quartz OSL sensitivity in fluvial systems: insights from transport mechanisms in the upper Yellow River - Ya Liu; Song-Xi Du; Jia-Fu Zhang; Xue Rui; Yu-He Shen; Jia-Jing Wang; Qing-Hao Ma; Zheng-Hao Gu (Geomorphology, 2026)

Seismic performance of Chinese pavilion-type timber frame with forked column: Experimental tests - Zuoshuai Sun; Hongtai Zhang; Sicheng Li; Rui Zhang; Ping Xiang; Liang-jiu Jia (Engineering Structures, 2026)

Polystyrene and its dissolved organic matter accelerate antibiotic resistance gene dissemination in anaerobic digestion by posing resistance pressure on functional microorganisms - Zixuan Zhang; Rui Wang; Zhibo An; Yiming Liu; Jiarui Zhao; Taishuo Zhang; Xiaoqian Ye; Peng Liu; Hanzhong Jia (Water Research, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Strengthening of MFC sensor performance by biomass materials: Characteristics and associated biological mechanisms - Rui Gan; Yingjie Zhou; Jia Chen; Hongbing Luo; Ke Zhang (Process Safety and Environmental Protection, 2026)

Biaxially oriented polyethylene film packing and hydrogen sulfide fumigation maintain postharvest quality of tomato fruits by reducing malondialdehyde levels and water loss - Le-Ying Yan; Pedro Garcia-Caparros; Jia-Xin Wang; Wan-Ken Chen; Xiong-Jie Wu; Dong-Bo Zhu; Rui Zhang; Zhao-Zhong Wang; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2026)

Multi-omics analyses identify the modulators COX6A1 and NAL as regulators of silk cocoon formation in Plutella xylostella - Rui-Chang Niu; Qing-Hui Zeng; Wen-Jing Wang; Jia Hu; Tong-Xian Liu; Shi-Ze Zhang (Pesticide Biochemistry and Physiology, 2026)

A novel multi-scale structural equivalent method for jointed rock masses and its application to slope stability analysis - Jia Wang; Wen Zhang; Han Yin; Rui Fu; Qi Sun; Jiali Han; Junqi Chen (International Journal of Rock Mechanics and Mining Sciences, 2026)

Dietary Haematococcus pluvialis powder enhances the growth and hepatopancreas and intestinal health of Leuciscus waleckii via NF-κB/Nrf2 pathway - Bei Xi; Tong-Tong Tan; Qi Sun; Ming-Xuan Zhang; Jia-Jing Wang; Rui Zhu; Deng-Lai Li; Li-Fang Wu (Fish & Shellfish Immunology, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Soil respiration and its temperature sensitivity on croplands in response to biotic and abiotic factors under straw and nitrogen fertilizer management - Ru Guo; Ruixuan Hao; Xiaoyi Yang; Rui Qian; Zijun Ma; Yunyun Yang; Peng Zhang; Zhikuan Jia; Yuncheng Liao; Xiaolong Ren; Xiaoli Chen (CATENA, 2026)

Genome-wide analysis of the sugarcane SUT gene family reveals ShSUT4 as a key regulator of abiotic stress responses - Xue-Ting Zhao; Ahmad Ali; Cui-Lian Feng; Ji-Shan Lin; Rui-Jie Wu; Shu-Zhen Zhang; Guang-Run Yu; Hai-Feng Jia; Yu-Qing Gong; Ting-Ting Zhao; Jun-Gang Wang (Theoretical and Applied Genetics, 2026)

Spatiotemporal dynamics of non-photosynthetic vegetation across China and their implications for carbon fluxes along climate gradients - Chunsheng Wang; Qingjiu Tian; Wenmin Zhang; Jia Tian; Lili Chang; Rui Zhang; Qianjing Li (Science China Earth Sciences, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Phaeovulum Molybdatiresistens sp. nov., a Molybdate-resistant Bacterium Isolated from Eutrophic Pond Water - Jianjun Song; Yuanshuo Qiu; Ke Ma; Yuelin Liu; Jia Wang; Yaqi Liu; Xiaolong Song; Kaiyue Wang; Jinhua Hu; Weidong Mu; Yanfang Zhao; Aijv Liu; et al. (Current Microbiology, 2026)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Targeting YBX1: A novel therapeutic strategy for gastric cancer through regulation of cellular senescence and mTOR signaling - Wenze Zhang; Yanjuan Jia; Anqi Wang; Rui Guo; Zhuomin Fu; Wanxia Wang (Tissue and Cell, 2025)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Biodegradable film combined with ploughing: An approach to improve the sustainability of rainfed spring maize production - Rui Qian; Luning Du; Wenjing Li; Wei Wang; Yang Zhang; Yujie Gao; Wenjing Feng; Jiaji Ding; Wenbo Lv; Pengyao Qin; Tie Cai; Xiaolong Ren; et al. (Soil and Tillage Research, 2025)

The effect of minimum temperatures on changes in river dissolved oxygen is more pronounced in the climate transition zone - Qin Zhang; Rui Xia; Kai Zhang; Haiming Li; Yan Chen; Ruining Jia; Jinghui Dou; Lina Li; Chao Yan; Xiang Li (Journal of Environmental Management, 2025)

Insights into the combined effect of N2H4 and NH2OH on CANON process in SBR: Nitrogen removal performance, stability of process and microbial community - Zi-Yue Li; Run-Mei Li; Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Zi-Jun Yan; Qian-Qian Zhang; Zai-Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Combined effects of high-fat diet feeding and Streptococcus agalactiae infection on lipid metabolism, antioxidant status, and immune response in tilapia (Oreochromis niloticus) - Rui Jia; Yiran Hou; Linjun Zhou; Chengfeng Zhang; Bing Li; Jian Zhu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

Process intensification of CO2 desorption by Higee technology: An industrial case study - Han-Zhuo Xu; Rui-Qi Jia; Yong Cai; Liang-Liang Zhang; Fei Gao; Guang-Wen Chu (Chemical Engineering Journal, 2025)

MXene triggers room-temperature 4D printing of advanced ionic hydrogels for sensitive electronic skin - Qinglong He; Chendong Zhao; Yuanjie Jiang; Jimei Liu; Xinyu Liu; Rui Jia; Cheng Yang; Mengzhou Liao; Yan Zhao; Desheng Kong; Valeria Nicolosi; Caofeng Pan; et al. (Chemical Engineering Journal, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Two undescribed constituents from Salvia castanea Diels and evaluation of their cytotoxic activity - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Tashi Tsering; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2025)

Multiscale responses of gap-graded soil under the combined effect of train vibration and seepage erosion - Dong-Mei Zhang; Hui-Hao Chen; Xiao-Chuang Xie; Si-Rui Chen; Zhao-Geng Chen; Jia-Ping Li (Transportation Geotechnics, 2025)

Higher ammonia oxidizing activity of comammox cooperates with ammonia-oxidizing bacteria to release N2O in river ecological restoration areas - Yuantao Wang; Shenghua Zhang; Rui Jia; Xin He; Ang Li; Dongdan Yuan (Journal of Environmental Management, 2025)

Enhanced electrocatalytic oxidation of high-salinity quaternary ammonium compound wastewater using CNTs-(Ru Ir O2)/Ti Anode - Hao-Tian Liu; Han-Qing Zhao; Yi-Rui Yang; Shuang Wu; Jia-Ping Huang; Rui-Han Yu; Hongcheng Bai; Aqiang Ding; Daijun Zhang; Peili Lu (Journal of Environmental Sciences, 2025)

Dynamic response of ceramic-reinforced metallic corrugated sandwich structures under combined blast-fragment loading - Chang-ye Ni; Cong Luo; Lu-sheng Qiang; Xin-yi Bai; Jia-le Wu; Jian-hong Zhang; Rui Zhang (Engineering Structures, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

Fe3+ modulated protein-based soft actuators for organic solvent working conditions: Spatiotemporal programmability, multi-terrain locomotion, self-sensing and full biodegradability - Shaorong Zong; Xiaohui Chu; Jia Kang; Cungang Gao; Pengxin Jia; Yue Sun; Ming Zhang; Kaiming Wang; Rui Nian; Wenfa Yu (Chemical Engineering Journal, 2025)

Prolonged sepsis triggers abnormal mitochondrial dynamics in the limb muscles and diaphragm - Chao Xiong; Fasheng Guan; Jianguo Feng; Jing Jia; Jumei Zhang; Rui Tu; Jie Li; Jun Zhou; Jianglin Wang; Li Liu (Molecular and Cellular Biochemistry, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Physiological and transcriptomic insights into the responses of juvenile Mytilus galloprovincialis under acute and chronic exposure to the toxic dinoflagellate Alexandrium tamarense - Ying Zhang; Jingyi Wang; Chuner Cai; Rui Jia; Peimin He (Marine Environmental Research, 2025)

Hydrological variability significantly influences aquatic biological integrity at the spatial scale in semi-arid watersheds - Lina Li; Rui Xia; Xinghui Xia; Ming Dou; Minhua Ling; Yan Chen; Jinghui Dou; Kai Zhang; Ruining Jia; Chao Yan (Journal of Hydrology, 2025)

Development of Palygorskite-CaIn2S4 composite for rapid Cr(VI) reduction under visible light - Yuanyuan Wang; Shijun Jia; Shiqiang Ding; Wenyan Zhang; Rui Shu; Yingfei Hu (Journal of Environmental Sciences, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Enhancing soil health in urban green spaces: The critical role of terrain and hydrological connectivity in nutrient redistribution - Pengcheng Lv; Yang Liu; Xiaoli Jia; Rui Li; Honglin Zhang; Yunlong Zhai; Tianyu Zhang (CATENA, 2025)

Sublethal deltamethrin induces transgenerational fitness costs in Neoseiulus agrestis (Karg) (Acari: Phytoseiidae): impaired parental reproduction and offspring development - Jing Chang; Shu-Lei Zhang; Cheng Wang; Xiao-Tong Fu; Zhi-Jia Huo; Rui-Xia Meng (Experimental and Applied Acarology, 2025)

Research on calibration transfer methods in coal quality spectral analysis across instruments and coal types - Jiaxuan Li; Jiaxin Yin; Rui Gao; Yan Zhang; Lei Zhang; Lei Dong; Weiguang Ma; Wangbao Yin; Suotang Jia (Analytica Chimica Acta, 2025)

Jingfang granule extends lifespan and healthspan in Caenorhabditis elegans: insights from RNA-seq analysis of genetic mechanisms - Taili Zhao; Yunhua Hou; Chuanjiao Feng; Rui Zhao; Honghua Li; Peipei Zhao; Mengmeng Wang; Jingli Ren; Yiwei Meng; Kuidong Xu; Jia Liu; Xin Yin; et al. (Biogerontology, 2025)

Desulfosporosinus sediminicola sp. nov., an acidophilic sulfate-reducing bacterium isolated from acidic sediments of a disused iron mine site - Sheng-Fang Jiang; Chu-Yi Zhang; Xuan-Wen Lao; Wei-Chao Jia; Tao-Tao Yang; Si-Yu Zhang; Ying-Ying Xie; Pei-Zhe Ye; Rui Lan; Zi-Xiang Lai; Qiang Yang; Li-Nan Huang (Antonie van Leeuwenhoek, 2025)

Iron and Ferritin Dyshomeostasis Intersect with Sex, Age, and Disease Severity in Amyotrophic Lateral Sclerosis - Xiaoge Xie; Peng Wu; Ting Wen; Rui Jia; Ronghua Zhang; Fangfang Hu; Jiaoting Jin; Xing Qin; Qiao Yi Chen (Journal of Molecular Neuroscience, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Effect and mechanism of Rice-Solanum nigrum L. rotation system inoculated with sulfate-reducing bacteria (SRB) and sulfur-oxidizing bacteria (SOB) for the remediation of Cd-contaminated paddy soil - Dan Zhang; Yipeng Gong; Rui Qin; SHAH ZAIB; Keyu Shang; Jia Xia; Liting Zhou; Yifei Xie (Journal of Hazardous Materials, 2025)

Enhanced phenanthrene degradation by a synthetically engineered E. coli consortium utilizing the SCRaMbLE for the evolution of key genes - Yibin Yang; Rui Chen; Zhiqiang Zhang; Yuke Qin; Attiqa Parveen; He Bai; Xiaoqiang Jia (Journal of Hazardous Materials, 2025)

Quantitative non-volatile sensometabolome of Longjing tea and discrimination of taste quality by sensory analysis, large-scale quantitative metabolomics and machine learning - Xujiang Shan; Linchi Niu; Qianting Zhang; Zhizhen Fang; Yuning Feng; Rui Liang; Zhenxing Xu; Shan Zhang; Le Chen; Weidong Dai; Qinghua Zhou; Yongwen Jiang; et al. (Food Chemistry, 2025)

Effect of non-Saccharomyces yeast combinations and lactic acid bacteria inoculation timing on fermentation performance and aroma quality of kiwifruit wine - Wangsheng Sun; Wanju Yan; Rou Cai; Zhendong Zhang; Pengfei Bi; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Fangyu Long; Jing Guo (Food Bioscience, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Tailoring reactivity in MOF derivatives via thermally induced amorphization: Synergistic crystalline/amorphous heterointerfaces for efficient 4-nitrophenol detoxification - Wenyao Zhang; Mian Wang; Rui Xiong; Kai Wei; Genping Zhu; Wei Ye; Wei Wang; Haijiao Xie; Peng Gao; Gan Jia (Chemical Engineering Journal, 2025)

Modulating band structure of MoO3 via W-doped for enhanced photo-induced charge transfer and SERS detection - Hongwen Cao; Yunpeng Cao; Jia He; Xin Xie; Zhijun Wang; Sen Sun; Rui Zhong; Lei Sun; Yihan Wang; Kun Zhang (Chemical Engineering Journal, 2025)

A novel forward osmosis nanocomposite membrane with g-C3N4 quantum dots fabricated on polyacrylonitrile electrospun nanofiber membrane for high-permeability and selectivity - Dibakar Pandaya; Jia-Rui Yang; Zhen-Liang Xu; Mateen Hedar; Ming-Xiao Zhang; Rui Jia; Rui Han; Muhammad Irfan; Liang Cheng; Mahesh Kumar Joshi (Chemical Engineering Journal, 2025)

The synergistic effects of entomopathogenic fungus Cordyceps javanica and parasitoid Tamarixia radiata in Asian citrus psyllid management - Pei-Ping Xu; Xin-Yi Chen; Jia-Rui Wang; Zi-Tong Lu; Marguerite Mukangango; Wen-Sang; Bao-Li Qiu; Li-He Zhang; Shaukat Ali (Crop Protection, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Unveiling anomalies in visual processing regions in obsessive-compulsive disorder: evidence from gray matter volume and functional connectivity analyses - Rui Liu; Fengxia Zhang; Pengchong Wang; Jia Luo; Yue Liu; Kaiyin Huang; Xiangyun Yang; Aihong Yu; Zhanjiang Li (Brain Imaging and Behavior, 2025)

An oral recombinant human type 5 adenovirus vector vaccine encoding the S protein of Type I feline coronavirus effectively protection against FCoV challenge in cats - Gu-nan Deng; Chang-zhan Xie; Ke-lei Zhou; Chun-sai He; Yuan-Zhen Ma; A.-jia Ake; Rui Guo; Kai Li; Chen Peng; Bin Zhang (Veterinary Microbiology, 2025)

Alterations in microbial-mediated methane, nitrogen, sulfur, and phosphorus cycling within paddy soil induced by integrated rice-fish farming - Yiran Hou; Rui Jia; Linjun Zhou; Liqiang Zhang; Sun Wei; Bing Li; Jian Zhu (Journal of Environmental Management, 2025)

Substrate type-driven differences in interfacial microbial community and pathogenic risk: Clay, microplastics and activated carbon - Taishuo Zhang; Wenfu Wang; Xiang Zhi; Xiaoqian Ye; Rui Wang; Jiarui Zhao; Jiamin Dai; Hong Qiang; Peng Liu; Hanzhong Jia (Gondwana Research, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Bonenncarpas A–K: Coumarin derivatives with anti-inflammatory activity from Boenninghausenia sessilicarpa - Gang-Zhong Zhou; Ruo-Xi Hu; Qi-Jing Fan; Chu-Chu Xi; Yan-Gang Cao; Jia-Rui Li; Zheng-Yu Cao; Chun-Lei Zhang (Phytochemistry, 2025)

Development of aroma attributes and volatile components during liquid-state fermentation of instant dark tea by Aspergillus niger - Haoran Sun; Yaling Cao; Rui Fang; Jia Li; Shanshan Shen; Shengshuo Zhang; Ranqin Fan; Jialin Fu; Feng Zou; Pengxiang Yue; Yu Wang; Xueling Gao (Food Bioscience, 2025)

Microfluidic-oriented assembly of MXene composite fibers for flexible zinc ion supercapacitors with high energy density - Fanyu Xie; Yuan Du; Menghan Chu; Xiaoyu Jia; Hui Cao; Rui Zhang; Hongwei Li; Mei Zhang (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Sex-Specific Association Between Urinary Metal and Serum Homocysteine Levels in Chinese Older Adults: A Study Based on the Yinchuan Community-Dwelling Elderly Cohort - Zhongyuan Zhang; Kai Wang; Siyu Duan; Yuqing Dai; Meiyan Li; Zhuoheng Shen; Pei He; Rui Wang; ZeYang Bai; JinHao Jia; Limeng Xiong; Xiaoyu Li; et al. (Exposure and Health, 2025)

Research on seismic performance and improvement of Chinese rural self-built houses - Jianxiong Zhang; Dewen Liu; Rui Sun; Yong Ding; Yunlong Zhao; Jia Wang; Weiwei Sun (Bulletin of Earthquake Engineering, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Effects of starvation-refeeding on antioxidant status, metabolic function, and adaptive response in the muscle of Cyprinus carpio - Wenrong Feng; Jianlin Li; Yuanfeng Xu; Gang Jiang; Shengyan Su; Zhihua Zhang; Rui Jia; Yongkai Tang (Aquaculture, 2025)

Multi-epitope vaccines Xlc and Ddc against Glaesserella parasuis infection in mice - Lu Dai; Jiajia Wan; Rui Zhang; Tingting Xie; Yizhen Jia; Zhichao Lu; Fuxian Zhang; Wenting Ke; Feng Liu; Liancheng Lei (Veterinary Microbiology, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Algicidal activity and mechanism of novel Bacillamide a derivative against red tide algae Skeletonema costatum and Prorocentrum minimum - Huili Li; Xiaoxue Li; Yi Liu; Ronglian Xing; Hongxia Zhang; Wenguang Jia; Lihong Chen; Rui Li; Zhen Yu; Zhihong Tang (Pesticide Biochemistry and Physiology, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

Adaptive sowing window strategy for improving grain filling and water loss characteristics of film-mulched maize in Northwest China - Xudong Zhang; Haixiang Xiong; Rui Wang; Junjie Li; Zhaoyun Dong; Zhikuan Jia; Qingfang Han (Field Crops Research, 2025)

Integrated rice-fish farming dynamically altered the metal resistances and microbial-mediated iron, arsenic, and mercury biotransformation in paddy soil - Yiran Hou; Rui Jia; Linjun Zhou; Liqiang Zhang; Wei Sun; Bing Li; Jian Zhu (Environmental Pollution, 2025)

Low-damage performance of rocking column bases with Belleville Springs for enhanced seismic resilience - Jiang-Yue Xie; Zhenduo Yan; Junrong Liu; Rui Zhang; Ping Xiang; Xianzhong Zhao; Gregory A. MacRae; G. Charles Clifton; Rajesh P. Dhakal; Shahab Ramhormozian; Geoffrey Rodgers; Pierre Quenneville; et al. (Engineering Structures, 2025)

Defect-repair in carbon for fast and stable potassium and sodium storage - Rui Ma; Yaxin Chen; Binyuan Zhang; Lili Ai; Changyu Leng; Mengjiao Xu; Dianzeng Jia; Nannan Guo; Luxiang Wang (Chemical Engineering Journal, 2025)

Effects of earthworms on the performance of Lolium multiflorum, soil properties and microbial communities in its root-zone soil under cadmium stress - Xiao-Gai Wang; Bing-Nan Zhao; Zi-Yang Xie; Zhi-Huan Chen; Zhi-Hang Liu; Xiao Chen; Bo-Yang Lu; Jia-Ning Liu; Rui Zhang; Chao Si (Plant and Soil, 2025)

The potential of golden apple snail (Pomacea canaliculata) meat meal as an alternative protein source for juvenile Chinese mitten crab (Eriocheir sinensis) - Wenxiang Yao; Chunyan Zhang; Rui Jia; Sitong Zhao; Weibo Jiang; Guoan Hua; Sizhe Zhao; Apeng Lin; Jianguo Wang; Quan Wang (Frontiers in Marine Science, 2025)
This study investigated the effects of replacing dietary fish meal (FM) with golden apple snail ( Pomacea canaliculata ) meat meal (PCM) on growth performance, non-specific immunity and intestinal health of juvenile Chinese mitten crab ( Eriocheir sinensis ). Four hundred juvenile Chinese mitten crabs (2.39 ± 0.03) g were randomly distributed into five groups in quadruplicate (20 crabs per tank), and each group was fed with diets that replaced FM with PCM at 0% (FM-20, containing 200 g/kg FM), 25% (FM-15), 50% (FM-10), 75% (FM-5), and 100% (FM-0) for 8 weeks, respectively. The results showed that the growth, whole body composition, digestive enzyme activities, antioxidant performance, non-specific immunity, intestinal histology and microbiota composition of FM-15 and FM-10 groups all reached the same level as the FM-20 group ( P > 0.05). While the replacement ratio reached 75%, the FCR was significantly increased and the peritrophic membrane thickness was significantly decreased ( P< 0.05). When 100% FM was replaced, significantly decreased the growth performance, serum antioxidant and immune enzyme activities, mid-intestine folds height, width and the peritrophic membrane thickness ( P< 0.05), and significantly increased the abundance of intestinal harmful bacteria Vibrio ( P< 0.05). In conclusion, PCM can effectively replace 50% dietary FM (100 g/kg) without negative effects on the growth performance, intestinal health, serum immune, and antioxidant indexes of juvenile E. sinensis .

Study on the effect of surfactant ethoxy content on the wettability adjustment of bituminous coal interface - Lei Fang; Jiangshi Zhang; Yunfei Liang; Linquan Tong; Jianguo Liu; Hongfu Jia; Xinyang Chen; Pengcheng Liu; Rui Xu (Journal of Environmental Chemical Engineering, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Highly efficient separation of anthracene and carbazole in crude anthracene by composite extractants with low viscosity - Yuanyuan Wang; Wenhai Zhang; Danting Wang; Rui Ma; Lili Ai; Mengjiao Xu; Dianzeng Jia; Nannan Guo; Luxiang Wang; Hong Meng (Chemical Engineering Journal, 2025)

Carboxymethyl chitosan/oxidized hyaluronic acid hydrogel-encapsulated hucMSC-derived exosomes for enhanced hepatic regeneration and post-hepatectomy applications - Qiuxia Zheng; Jia Yao; Zongbin Sun; Rui Li; Yue Zhang; Pan Jiang; Ye Xie; Xiaojing Song; Hongfa Sun; Dan Zhu; Haixu Ni; Xun Li (Carbohydrate Polymers, 2025)

“Off-on-off”-based metal-organic framework fluorescent sensor for adenosine triphosphate detection and tumor microenvironment-triggered drug release - Tianqian Jia; Ke Wang; Xiaojuan Li; Cuixia Ma; Du Yang; Rui Wang; Yanyan Zhang; Sicheng Zhai; Shuming Li (Analytica Chimica Acta, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Monitoring dust retention variations in different functional zones based on leaf magnetism and the influence of green belt spatial layouts on leaf dust retention - Ziwei Tao; Shuxuan Li; Bo Wang; Yi Xie; Rui Wang; Linglin Hu; Jia Jia; Junhui Zhang (Environmental Monitoring and Assessment, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Revealing the key role of interfacial oxygen activation over CoMn2O4@MnO2 in the catalytic oxidation of acetone - Cangpeng Shan; Yan Zhang; Ning Hou; Qinwei Jia; Xinyu Hou; Yunchong Wang; Rui Han; Caixia Liu; Weichao Wang; Qingling Liu (Journal of Hazardous Materials, 2025)

Structural evolution of Ni-Ce bimetallic alloy on Al2O3 support in methane dry reforming: Achieving sustainability and high-efficiency reaction through cerium modulation strategy - Xu Ma; Wei-Wei Yang; Jia-Rui Zhang; Xin-Yuan Tang (Fuel, 2025)

Gelation melioration of clam Meretrix meretrix surimi based on the interactions with different plant/animal proteins - Lin-Da Zhang; Yue Liu; Ying-Rui Wang; Tian-Qi Zhou; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

The Impact of Different Mating Systems on Locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Ruo-Xi Wang; Jia-Xin Xu; Kai-Chen Weng; An-Xin Wang; Hao Huang; Yu-Yuan Lu; Yi-Jie Chen; Yu-Chen Wang (Journal of Insect Behavior, 2025)

Soil degradation: A global threat to sustainable use of black soils - Rui LI; Wenyou HU; Zhongjun JIA; Hanqiang LIU; Chao ZHANG; Biao HUANG; Shunhua YANG; Yuguo ZHAO; Yongcun ZHAO; Manoj K. SHUKLA; Miguel Angel TABOADA (Pedosphere, 2025)

On using an aerosol thermodynamic model to calculate aerosol acidity of coarse particles - Zhengyang Fang; Shuwei Dong; Chengpeng Huang; Shiguo Jia; Fu Wang; Haoming Liu; He Meng; Lan Luo; Yizhu Chen; Huanhuan Zhang; Rui Li; Yujiao Zhu; et al. (Journal of Environmental Sciences, 2025)

UPLC-HDMS revealed numerous novel compounds in soybean crude oil - Zhaohui Sun; Feng Dong; Rui Zhang; Xinyu Song; Xiaocai Huang; Yingran Dong; Xiaofei Jia; Shunian Luo; Ying Li; Maoqing Wang (Food Chemistry, 2025)

Gelation improvement of low-salt Chinese shrimp (Fenneropenaeus chinensis) surimi gel by L-arginine - Yue Liu; Lin-Da Zhang; Ying-Rui Wang; Tian-Qi Zhou; Yu-Qiao Wang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Revealing the combined effect of hydroxylamine and hydrazine on nitrogen removal performance of completely autotrophic nitrogen removal over nitrite (CANON) process - Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Bioresource Technology, 2025)

Strengthening H2 gas–liquid mass transfer using superaerophobic cathodes for enhanced methane production from CO2 in H2-mediated microbial electrosynthesis system - Jia-Yao Gao; Wen-Fang Cai; Ji-Rui Bai; Yu-Cheng Zhu; Yu-Xiao Zhang; Sheng Wang; Kun Guo; Qing-Yun Chen; Yun-Hai Wang (Bioresource Technology, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Physio-biochemical and molecular mechanisms of low nitrogen stress tolerance in peanut (Arachis hypogaea L.) - Xiangjun Kong; Rui Wang; Peipei Jia; Hengbin Li; Aziz Khan; Ali Muhammad; Sajid Fiaz; Qunce Xing; Zhiyong Zhang (Plant Molecular Biology, 2025)

Spatial Characteristics of the Plasma Spark Source Wavelet - Jia Wei; Xiaozhu Hao; Jing Feng; Rui Yang; Lei Xing; Huaishan Liu; Wei Wang; Zhiqiang Wu; Dong Zhang; Linwei Li (Journal of Ocean University of China, 2025)

A new benzophenone derivative from Aspergillus fumigatus WJ-131 - Jia-Qi Liu; Sheng-Qi Zhang; Xiu-Hong Wu; Shuai-Xing Liu; Rui-Dang Yang; Liang Deng; Le Cai (Natural Product Research, 2025)

A new anti-inflammatory thujane monoterpenoid glycoside ester from Pittosporum heterophyllum Franch - Jia-Qi Ding; Sheng-Nan Guan; Yu-Feng Zhang; Zhao-Xuan Wang; Wei-Zhen Kong; Jun-Rui Ren; Xiu-Yun Zhang (Natural Product Research, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Design method of simplified dynamic test model for high-rise building with underground structures considering nonlinear behavior similarity - Rui Wang; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Yao-Zhong Cui; Han Zhang; Jia-Long Li (Engineering Structures, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Flower-structured CoP@MoS2-x S-scheme heterojunction photocatalysts for enhanced hydrogen evolution and selective biomass oxidation - Jia Zhang; Jiliang Ma; Rui Cui; Weikang Ling; Min Hong; Runcang Sun (Chemical Engineering Journal, 2025)

In vivo quantification of polyphosphate in Microcystis aeruginosa using DAPI staining - Rui Zhu; Xiao Tan; Zhipeng Duan; Yijia Wei; Imran Ali; Jiang Huang; Jia Liang; Jianyong Hu; Jiazhi Zhang; Zixin Zhou (Algal Research, 2025)

Effects of high vp28 expression in Synechocystis sp. PCC6803 constructed by homologous recombination on immunity and antioxidant capacity of white spot syndrome virus infected Litopenaeus vannamei - Ning Ding; Jia Yang; Hang Zhang; Xianghong Qi; Fangyuan Liu; Yifei Shen; Rui Jia (Aquaculture International, 2025)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Tailoring Na2FePO4F nanoparticles as the high-rate capability and Long-life cathode towards fast chargeable sodium-ion full batteries - Weihuang Wang; Shuhui Li; Yixin Jia; Dongqiang Cao; Rui Liu; Zheng Wang; Zicheng Xie; Lantian Zhang; Liangbing Wang (Chemical Engineering Journal, 2024)

Screening and tentatively identifying of volatile hazards of desiccant and deoxidizer in food package - Hongyi Liu; Rui Fan; Siting Li; Hong Zhang; Zhou Chen; Aijin Ma; Yingmin Jia (Food Control, 2024)

Perovskite nanocrystals photo-initiated in situ encapsulation for optical tracking - Xiao’e Jia; Tongyu Shi; Qingyuan Zhang; Hao Huang; Paul K. Chu; Xue-Feng Yu; Rui He (Chemical Engineering Journal, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

MSC-mediated mitochondrial transfer restores mitochondrial DNA and function in neural progenitor cells of Leber’s hereditary optic neuropathy - Rui Wang; Feixiang Bao; Manjiao Lu; Xiaoyun Jia; Jiahui Xiao; Yi Wu; Qingjiong Zhang; Xingguo Liu (Science China Life Sciences, 2024)

Analysis of factors affecting microbial degradation of cyanobacterial toxins based on theoretical calculations - Jianglong Ling; Ye Ruan; Congchao Xu; Di Liu; Bowen Shi; Yihong Yang; Zihao Jia; Tianyu Zhang; Mingxuan Guo; Rui Li; Xixi Li (Environmental Geochemistry and Health, 2024)

Water pollution control promotes sustainable water use in Yangtze River Economic Belt——from water footprint perspective - Ruining Jia; Zhongwen Yang; Rui Xia; Yan Chen; Lu Wang; Chen Yang; Hui Zhang; Qiang Hu; Xiang Li; Yingze Yin; Nixi Zhong; Chao Yan (Environment, Development and Sustainability, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

Enhanced nitrogen and phosphorus removal by iron-manganese mediated autotrophic denitrification in electrochemical system and the underlying mechanisms - Rui Gan; Ke Zhang; Hongbing Luo; Jia Chen (Process Safety and Environmental Protection, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Association between heatwaves and risk and economic burden of injury related hospitalizations in China - Cheng Zhao; Yushu Huang; Yibin Cheng; Rui Zhang; Yu Wang; Shilu Tong; Jiang He; Jia Guo; Fan Xia; Yonghong Li; Xiaoyuan Yao (Environmental Research, 2024)

Reason and control strategy for denitrification and anammox sludge flotation in nitrogen removal process: Mechanisms, strategies and perspectives - Xin Ma; Xin-Rui Zhang; Ying-Jun Sun; Zhi-Han Xi; Jin-Ze Liu; Ze-Tong Feng; Jia-Min Zhou; Xin-Tao Liu; Ying Wang; Ren-Cun Jin; Qian-Qian Zhang (Environmental Research, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

Facile generation of unsaturated-coordinated and atomically-dispersed hafnium active sites for the highly efficient catalytic transfer hydrogenation of levulinic acid - Rulu Huang; Yue Wang; Feiyi Chen; Huai Liu; Rui Zhang; Wenlong Jia; Lincai Peng; Yong Sun; Junhua Zhang (Chemical Engineering Journal, 2024)

Effects of slow temperature acclimation of photosynthesis on gross primary production estimation - Jia Bai; Helin Zhang; Rui Sun; Yuhao Pan (Agricultural and Forest Meteorology, 2024)

A nationwide characterization of organochlorine pesticides (OCPs) in livestock and poultry food products across China: Residual levels, origin and the associated health risks - Lu Chen; Yongzhong Qian; Xu Wang; Qi Jia; Rui Weng; Xinglian Zhang; Yun Li; Jing Qiu (Chemosphere, 2024)

The role of pantothenic acid in alleviating hypoxia-induced liver injury of sub-adult grass carp (Ctenopharyngodon idellus): Possible mechanisms and implication - Yan Xia; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Jia-Yong Tang; Rui-Nan Zhang; Lu Zhang; Hai-Feng Mi; Lin Feng (Aquaculture, 2024)

Simultaneous removal of nitrate nitrogen and ammonium nitrogen by partial denitrification coupled with anammox synergy by zero-valent iron - Jia-Min Zhou; Ying-Jun Sun; Zhi-Han Xi; Zu-Gang Liao; Xin Ma; Ze-Tong Feng; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Journal of Cleaner Production, 2024)

Benefits and costs: Understanding the influence of heavy metal pollution on environmental adaptability in Strauchbufo raddei tadpoles through an energy budget perspective - Xueying Zhang; Rui Su; Yuting Qin; Yue Shen; Lun Jia; Wenya Zhang (Environmental Pollution, 2024)

Analytical calculation method of circular-section rocking steel piers under horizontal cyclic load - Hanqing Zhuge; Jianian Wen; Zhenlei Jia; Qiang Zhang; Qiang Han; Rui Du (Engineering Structures, 2024)

Feasibility and safety of percutaneous intramyocardial septal cryoablation: A canine model with 6-month follow-up - Xiaonan Lu; Jing Li; David H. Hsi; Juan Zhang; Yupeng Han; Shengjun Ta; Jing Wang; Jin He; Jia Zhao; Chao Han; Lu Yao; Xumei Ou; et al. (Cryobiology, 2024)

Efficient photocatalytic degradation of 24 imidazolium ionic liquids in an N-ZnO/simulated sunlight irradiation system and its mechanism - Jiaoqin Liu; Jingjing Zhang; Mengye Jia; Rui Ma; Ruijuan Qu; Zunyao Wang; Zhaoguo Liu; Yu Jiang; Haoxiang Zhang; Yujia Bai; Riya Jin; Yina Qiao; et al. (Chemical Engineering Journal, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Effects of anaerobic oxidation of methane (AOM) driven by iron and manganese oxides on methane emissions in constructed wetlands and underlying mechanisms - Ke Zhang; Rui Gan; Yangxingyue Li; Wei Chen; Dandan Ma; Jia Chen; Hongbing Luo (Chemical Engineering Journal, 2024)

A multi-spatial scale analysis of anthropogenic nitrogen and phosphorus inputs in a large river basin: environmental effect and policy impact - Chenning Deng; Zeqian Zhang; Chaozheng Zhang; Rui Xu; Chong Nie; Qingjia Meng; Tiansen Zou; Hong Li; Jia Wu; Queping Yang (Regional Environmental Change, 2024)

Metformin improves cognitive dysfunction through SIRT1/NLRP3 pathway–mediated neuroinflammation in db/db mice - Tian Hu; Jun-Wen Wei; Jia-Yi Zheng; Qing-Yi Luo; Xin-Rui Hu; Qun Du; Ye-Feng Cai; Shi-Jie Zhang (Journal of Molecular Medicine, 2024)

Exploring the relationship between land use change patterns and variation in environmental factors within urban agglomeration - Rui Xiao; Hanyu Yin; Ruoxin Liu; Zhonghao Zhang; Sukhbaatar Chinzorig; Kun Qin; Wenfang Tan; Yi Wan; Zhi Gao; Chen Xu; Lumeng Liu; Tao Jia (Sustainable Cities and Society, 2024)

Compositional analysis and quantitative evaluation of organic emissions from asphalt materials: Improvements and refinements - Rui Zhang; Naipeng Tang; Hongzhou Zhu; Yuan Xi; Huailei Cheng; Jia Liu; Rui Li (Journal of Cleaner Production, 2024)

Tuning electronic environment of B sites in boron carbonitride nanoribbon boosts catalytic activity of reducing N2 to NH3 - Kai Zhang; Rui Zhang; Yuxin Cui; Jiayin Shang; Xueling Wei; Sumin Wang; Siqin Jia; Ke Qin; Haiyan Zhang; Hongyan Wang; Taotao Ai; Qiguan Wang (Fuel, 2024)

Stochastic process is main factor to affect plateau river fish community assembly - Xiaoxuan Li; Qigong Xu; Rui Xia; Nan Zhang; Shuping Wang; Sen Ding; Xin Gao; Xiaobo Jia; Guangxia Shang; Xiaofei Chen (Environmental Research, 2024)

Forecasting the cost premium of certified green building in China: A cutting-edge methodology incorporating radial basis function neural network and various optimization algorithms - Rui Liang; Jia Liang; Zhang Ming (Energy and Buildings, 2024)

Oxygen-driven closing pore formation in coal-based hard carbon for low-voltage rapid sodium storage - Rui Ma; Yaxin Chen; Qian Li; Binyuan Zhang; Feifei Chen; Changyu Leng; Dianzeng Jia; Nannan Guo; Luxiang Wang (Chemical Engineering Journal, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Integrated Rice–Fish Culture Alters the Bacterioplankton Community and Its Assembly Processes - Weixu Diao; Julin Yuan; Rui Jia; Yiran Hou; Liqiang Zhang; Bing Li; Jian Zhu (Fishes, 2024)
The rice–fish co-culture is an important model of carp farming in China; however, research on the dynamics and assembly of water bacterial communities in this system remains limited. Therefore, this study aimed to explore the dynamics and assembly of bacterial communities, as well as their correlation with environmental factors in paddy water. For these purposes, this study was divided into two groups: a rice–carp co-culture (WRC) group and a rice monoculture (WRM) group, with 20 rice fields in each group. After 60 days of farming, the concentrations of NH4+-N, NO2−-N, TN, and PO43− were significantly higher in the WRC group than those in the WRM group. Alpha diversity analysis showed that the Shannon index in the WRC group was significantly decreased compared with the WRM group. At the phylum level, the relative abundance of Actinobacteria significantly increased, while the relative abundance of Proteobacteria and Bacteroidetes significantly decreased in the paddy water of the WRC group. The neutral community model (NCM) indicated that a random process played a dominant role in the construction of bacterial communities in the two groups, and common carp cultivation increased migration rates, thereby affecting community assembly. The co-occurrence network displayed that common carp cultivation led to looser interactions between bacterial communities. In addition, the contents of nutrients significantly affected the abundance of bacteria in paddy water. In summary, carp cultivation decreased the diversity of bacteria and changed the relative abundance of dominant bacteria, thereby affecting the stability and assembly of bacterial communities.

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Effects of Different Stocking Densities on the Growth, Antioxidant Status, and Intestinal Bacterial Communities of Carp in the Rice–Fish Co-Culture System - Weixu Diao; Rui Jia; Yiran Hou; Jianyou Gong; Liqiang Zhang; Bing Li; Jian Zhu (Fishes, 2024)
Common carp (Cyprinus carpio) is a freshwater fish commonly farmed in rice fields, yet there were few studies on the intestinal functions and microbial community structure of common carp in the rice–carp co-culture system. Therefore, this study aimed to explore the effects of different stocking densities on the growth, antioxidant status, and intestinal bacterial composition of common carp in this system. This study was divided into three different stocking densities, including low density (LD, 10 fish, 52.9 g/m2), medium density (MD, 20 fish, 105.8 g/m2), and high density (HD, 30 fish, 158.7 g/m2), with a culturing period of 60 days. The results indicated that HD treatment inhibited the growth of common carp, as evidenced by the reduced final weight, WG, and SGR. In serum, the TG content in the HD group and the Cor content in the MD group were significantly increased. Meanwhile, HD treatment induced oxidative stress, manifesting specifically as increased SOD and CAT activities in the intestine or serum while reducing Gpx, GSH, and T-AOC in the serum. The 16S rDNA analysis indicated that the Simpson and Shannon indices of intestinal microbiota in the HD group were significantly higher than those in the LD group. At the phylum level, Proteobacteria, Cyanobacteria, and Firmicutes were dominant microbial communities in two groups. In addition, there was a significant difference between the two groups in the abundances of Actinobacterota and Bifidobacterium. Based on growth performances, biochemical indicators, and microbial diversity in rice–carp co-culture, low density (52.9 g/m2) may be more suitable in the rice–carp co-culture systems. In summary, this study contributes to a better understanding of common carp response to different stocking densities in the rice–carp co-culture system.

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

3D-interconnected N-doped porous carbon with hierarchical pore structure as a high-efficiency catalyst for H2S oxidation at room temperature - Yan Huang; Qiang Zuo; Rui Wang; Ruifang Zhang; Yike Zhang; Jia Song; Jingzhen Wang; Boqiang Gao; Shuanglong Ma (Journal of Cleaner Production, 2024)

Farmers' cooperation preference for solar composting chamber —— From farmers’ multi-dimensional heterogeneity perspective - Yajuan Jia; Rui Shi; Xinqi Zhang; Jiapeng Chen; Jun Gao (Journal of Cleaner Production, 2024)

Gold nanocluster-based ratiometric fluorescence immunoassay for broad-spectrum screening of five eugenols - Lin Luo; Zhen-Xi He; Bao-Zhu Jia; Rui-Yao Kang; Wen-Feng Zhang; Ri-Ming Huang; Zhen-Lin Xu (Analytica Chimica Acta, 2024)

Cadmium interacts with nitrogen level and nitrogen form to affect the growth of an invasive plant Alternanthera philoxeroides - Dan Li; Xiao-Gai Wang; Jia-Xin Yang; Yu-Fei Hu; Wen-Yue Lyu; Jun-Cai Xin; Rui Zhang; Zhi-Huan Chen; Chao Si (Aquatic Ecology, 2024)

A newly defined latest Carboniferous-Permian ridge subduction in the southern Altaids: Insights from adakitic, S-type, and I-type granitoids in the northern East Junggar (NW China) - Jingmin Gan; Wenjiao Xiao; Qigui Mao; Hao Wang; He Yang; Miao Sang; Xiaoliang Jia; Yin Liu; Zhiyong Zhang; Zhou Tan; Rui Li (International Geology Review, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Role and action mechanisms of miR-149 and miR-31 in regulating function of pig cumulus cells and oocytes - Jia-Shun Wu; Shuai Gong; Min Zhang; Rui-Jie Ma; Hui-Li Wang; Ming-Jiu Luo; Nan He; Jing-He Tan (Theriogenology, 2024)

Bacterial community in the metal(loid)-contaminated marine vertical sediments of Jinzhou Bay: Impacts and adaptations - Yongbin Li; Rui Zhang; Guoqing Ma; Mingyi Shi; Yimei Xi; Xiaojun Li; Shaofeng Wang; Xiangfeng Zeng; Yongfeng Jia (Science of The Total Environment, 2024)

Integrated machine learning reveals aquatic biological integrity patterns in semi-arid watersheds - Lina Li; Rui Xia; Ming Dou; Kai Zhang; Yan Chen; Ruining Jia; Xiaoxuan Li; Jinghui Dou; Xiang Li; Qiang Hu; Hui Zhang; Nixi Zhong; et al. (Journal of Environmental Management, 2024)

Hollow glass microspheres incoporated conjugated microporous polymers composite aerogels for sustainable evaporation - Jiaxuan Zhou; Xiaoyin Cao; Yanju Jing; Jia Zhang; Hanxue Sun; Jiyan Li; Rui Jiao; An Li (Chemical Engineering Journal, 2024)

Somatic Embryogenesis in Taxodium Hybrid ‘zhongshanshan’, an Opportunity to Propagate an Ecologically Friendly Species - Tingting Chen; Xiaoyu Jia; Rui Zhang; Yan Lu; Chaoguang Yu; Yunlong Yin; Jianfeng Hua; David Creech (Journal of Plant Growth Regulation, 2024)

Influence of stratification and wind forcing on the dynamics of Lagrangian residual velocity in a periodically stratified estuary - Fangjing Deng; Feiyu Jia; Rui Shi; Shuwen Zhang; Qiang Lian; Xiaolong Zong; Zhaoyun Chen (Ocean Science, 2024)
Wind and stratification play pivotal roles in shaping the structure of the Lagrangian residual velocity (LRV). However, the intricate dynamics by which wind and stratification modify the LRV remain poorly studied. This study derives numerical solutions of LRV components and eddy viscosity subcomponents to elucidate the dynamics within the periodically stratified Pearl River estuary. The vertical shear cross-estuary LRV (uL) is principally governed by the interplay among the eddy viscosity component (uLtu), the barotropic component (uLba), and the baroclinic component (uLgr) under stratified conditions. During neap tides, southwesterly winds notably impact uL by escalating uLtu by an order of magnitude within the upper layer. This transforms the eastward flow dominated by uLtu under wind influence into a westward flow dominated by uLba in upper shoal regions without wind forcing. The along-estuary LRV exhibits a gravitational circulation characterized by upper-layer outflow engendered by a barotropic component (vLba) and lower-layer inflow predominantly driven by a baroclinic component (vLgr). The presence of southwesterly winds suppresses along-estuary gravitational circulation by diminishing the magnitude of vLba and vLgr. The contributions of vLba and vLgr are approximately equal, while the ratio between uLba and uLgr (uLtu) fluctuates within the range of 1 to 2 in stratified waters. Under unstratified conditions, LRV exhibits a lateral shear structure due to differing dominant components compared to stratified conditions. In stratified scenarios, the eddy viscosity component of LRV is predominantly governed by the turbulent mean component, while it succumbs to the influence of the tidal straining component in unstratified waters.

Mechanisms of the novel pesticide sodium dodecyl benzene sulfonate in the mitigation of protozoan ciliated pathogens during microalgal cultivation - Gaojingwen Sun; Ruiqi Jia; Yan Zhang; Zhaoji Zhang; Yunlong Wang; Rui Ma; Yaxin Wang; Zhiyang Jiang; Mingjian Liu; Yong Jiang (Marine Pollution Bulletin, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Effects of antimicrobial peptides from dietary Hermetia illucens larvae on the growth, immunity, gene expression, intestinal microbiota and resistance to Aeromonas hydrophila of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yong-Qi Meng; Jia-Jun Li; Xiu-Xia Zhang; Jun-Tao Li; Jia-Rui Xu; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Microplastics provide new hotspots for frequent transmission of antibiotic resistance genes during anaerobic digestion of sludge containing antibiotics - Yinping Xiang; Weiping Xiong; Zhaohui Yang; Rui Xu; Yanru Zhang; Meiying Jia; Haihao Peng; Lele He; Chengyun Zhou (Chemical Engineering Journal, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Correction to: A new strategy for groundwater level prediction using a hybrid deep learning model under Ecological Water Replenishment - Zihao Jia; Qin Zhang; Bowen Shi; Congchao Xu; Di Liu; Yihong Yang; Beidou Xi; Rui Li (Environmental Science and Pollution Research, 2024)

A new strategy for groundwater level prediction using a hybrid deep learning model under Ecological Water Replenishment - Zihao Jia; Qin Zhang; Bowen Shi; Congchao Xu; Di Liu; Yihong Yang; Beidou Xi; Rui Li (Environmental Science and Pollution Research, 2024)

SAR image classification using deep features and neighborhood heterogeneity confidence refined spatial constraints - Anjun Zhang; Linsheng Huang; Lu Jia; Rui Ruan; Jun Wang (International Journal of Remote Sensing, 2024)

Predictions of seismic response for sheet-pile wall in liquefiable deposit within LEAP 2022 using the CycLiq constitutive model - Bin Hu-Yan; Rui Wang; Jia-ke Yu; Jian-Min Zhang (Soil Dynamics and Earthquake Engineering, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Engineering extracellular electron transfer to promote simultaneous brewing wastewater treatment and chromium reduction - Deguang Wu; Baocai Zhang; Sicheng Shi; Rui Tang; Chunxiao Qiao; Teng Li; Jichao Jia; Meiyi Yang; Xiaoguang Si; Yifei Wang; Xi Sun; Dongguang Xiao; et al. (Journal of Hazardous Materials, 2024)

Integrated straw-derived biochar utilization to increase net ecosystem carbon budget and economic benefit and reduce the environmental footprint - Ru Guo; Rui Qian; Muhammad Asad Naseer; Fei Han; Peng Zhang; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Field Crops Research, 2024)

Excellent solar-driven interface evaporation by an oil repellence Janus photothermal membrane for oily wastewater treatment - Wenwen Luo; Jia Zhang; Meichen Liu; Anli Yi; Rui Jiao; Zhaoqi Zhu; Jiyan Li; Hanxue Sun; An Li (Chemical Engineering Journal, 2024)

Scrub-vegetation cover impact on soil water migration and temperature change during freeze–thaw events in sandy desert soils of northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Ruiting Jia (CATENA, 2024)

Entomopathogenic fungal-derived metabolites alter innate immunity and gut microbiota in the migratory locust - Wei Zhang; Chen Jia; Lian-Sheng Zang; Maiqun Gu; Rui Zhang; Ioannis Eleftherianos; Amr A. Mohamed (Journal of Pest Science, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Can straw recycling achieve sustainable agriculture at the smallholder level? A case in a semi-arid region - Rui Qian; Ru Guo; Qingxuan Yang; Muhammad Asad Naseer; Baoping Sun; Longlong Wang; Jian Zhang; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Journal of Cleaner Production, 2024)

Change of soil bacterial communities in chemically stabilized chromium contaminated soils in an accelerated aging experiment - Linying Yao; Yuning He; Peng Zhao; Zhihao Xie; Longfei Jiang; Danni Li; Yueqiao Liu; Rui Ma; Jianli Jia; Dayi Zhang (Journal of Environmental Chemical Engineering, 2024)

An interpenetrating polymer networks based on polydivinylbenzene/aminated polyglycidyl methacrylate with better decolorization performance toward reducing sugar solution - Junwei Zhang; Changchun Rui; Caijing Jia (Food Chemistry, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Effects of dietary chitosan oligosaccharide on the growth, intestinal microbiota and immunity of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yan-Lei Cao; Jia-Rui Xu; Xiu-Xia Zhang; Jia-Jun Li; Jun-Tao Li; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Involvement of TLRs/NF-κB/ESE-1 signaling pathway in T-2 toxin-induced cartilage matrix degradation - Yawen Shi; Rui Wang; Yanan Li; Yixin Cui; Ying He; Hui Wang; Yinan Liu; Meng Zhang; Yonghui Chen; Mingzhao Jia; Kunpan Chen; Xingran Ruan; et al. (Environmental Pollution, 2024)

The lncRNA20718-miR6022-RLPs module regulates tomato resistance to Phytophthora infestans - Jia-hui Zhang; Hong-bo Wei; Yu-hui Hong; Rui-rui Yang; Jun Meng; Yu-shi Luan (Plant Cell Reports, 2024)

Performance analysis of microbial fuel cell - membrane bioreactor with reduced graphene oxide enhanced polypyrrole conductive ceramic membrane: Wastewater treatment, membrane fouling and microbial community under high salinity - Rui Wang; Hong You; Binghan Xie; Guoyu Zhang; Jing Zhu; Weirun Li; Xinan Dong; Qiqing Qin; Mengying Wang; Yi Ding; Haili Tan; Yuhong Jia; et al. (Science of The Total Environment, 2024)

Perturbation of autophagy pathways in murine alveolar macrophage by 2D TMDCs is chalcogen-dependent - Xiaofei Zhou; Weitao Jin; Rui Zhang; Xuan Mao; Jianbo Jia; Hongyu Zhou (Journal of Environmental Sciences, 2024)

Novel insights into mass transfer-controlled radical-mediated co-pyrolysis of lignin with typical plastics - Yuyang Fan; Chao Liu; Zhengxue Zhang; Jia Ouyang; Fuli Deng; Ruixue Zhao; Huiyan Zhang; Rui Xiao (Chemical Engineering Journal, 2024)

1,4-Dioxane intervention enables simultaneous valorization of biomass-based C5 and C6 sugars to furfural over Hβ zeolite - Yujia He; Rui Zhang; Weipeng Song; Huai Liu; Junhua Zhang; Wenlong Jia; Lincai Peng (Chemical Engineering Journal, 2024)

Facile synthesis of bead-chain structured MWCNTs@CeO2 with oxygen vacancies-rich for promoting electrochemical energy storage - Xiao-Man Cao; Jia-Qi Chen; Xin-Rui Zhao; Hao Ge; Daliang Liu; Qiong Wu; Zhi-Jia Sun; Qingguo Zhang (Chemical Engineering Journal, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

Solutions on the periodic background and transition state mechanisms for the higher-order Chen–Lee–Liu equation - Jia-Xue Niu; Rui Guo; Jian-Wen Zhang (Wave Motion, 2023)

Microwave assisted synthesis of PQ-GDY@NH2-UIO-66(Zr) for improved photocatalytic removal of NO under visible light - Qingyu Yang; Shuangjun Li; Rui Liang; Lei Gao; Shao Zhang; Junfen Jia; Yiran Liu; Rundong Lyv; Guisheng Li; Shengxiong Xiao; Dieqing Zhang (Journal of Environmental Sciences, 2023)

Sources and solubility of aerosol phosphorus at a coastal site in northern China: Coarse versus fine particles and spring versus winter - Shuwei Dong; Huanhuan Zhang; Padmaja Krishnan; Shiguo Jia; Chengpeng Huang; Fu Wang; Lan Luo; Feng Wang; He Meng; Yujiao Zhu; Rui Li; Mingjin Tang (Atmospheric Environment, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Single-cell transcriptome analysis revealing the intratumoral heterogeneity of ccRCC and validation of MT2A in pathogenesis - Jie Wang; Zili Zuo; Zongze Yu; Zhigui Chen; Xiangdi Meng; Zhaosen Ma; Jiqiang Niu; Rui Guo; Lisa Jia Tran; Jing Zhang; Tianxiao Jiang; Fangdie Ye; et al. (Functional & Integrative Genomics, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Dietary oregano essential oil supplementation alters meat quality, oxidative stability, and fatty acid profiles of beef cattle - Pengjia He; Yu Lei; Ke Zhang; Rui Zhang; Yunpeng Bai; Zeming Li; Li Jia; Jinping Shi; Qiang Cheng; Yannan Ma; Xiaoqiang Zhang; Lishan Liu; et al. (Meat Science, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Application of enzymatically treated Artemisia annua L. on adult grass carp (Ctenopharyngodon idella): Improved growth performance, intestinal antioxidant capacity and apical junctional complex - Qin-Qin Dai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; He-Qun Shi; Lu Zhang; Hai-Feng Mi; Jia-Yong Tang; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Flow backward alleviated the river algal blooms - Yan Chen; Rui Xia; Ruining Jia; Qiang Hu; Zhongwen Yang; Lu Wang; Kai Zhang; Yao Wang; Xiaojiao Zhang (Water Research, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Metagenomic analysis reveals microbial metabolic potentials alterations under antibiotic stress during sludge anaerobic digestion - Yinping Xiang; Weiping Xiong; Rui Xu; Zhaohui Yang; Yanru Zhang; Meiying Jia; Haihao Peng (Journal of Environmental Chemical Engineering, 2023)

mARC dependent NO synthesis activates CanA-Relish-AMPs signal pathway in Eriocheir sinensis during nitrite stress - Rui Jia; Liangmin Zheng; Lihua Zhang; Xin Huang; Qian Ren (Fish & Shellfish Immunology, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Damage detection of foundation pile in high-pile wharf based on statistical high-order moment of dynamic response under regular wave excitation - Rui-hu Zhu; Qi-ming Wang; Jin-hai Zheng; Hai-kun Zeng; Jia-bao Zhang; Yan Hu; Cheng-ming Li (Ocean Engineering, 2023)

Integrated insight into the molecular mechanisms of selenium-modulated, MPP+-induced cytotoxicity in a Parkinson’s disease model - Wen Liu; Feiyang Zhang; Wu Liang; Kaixin Huang; Chenguang Jia; Jie Zhang; Xiang Li; Wei Wei; Rui Gong; Jincao Chen (Journal of Trace Elements in Medicine and Biology, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Enhanced anode electrochemiluminescence in split aptamer sensor for kanamycin trace monitoring - Xiaoyue Zhang; Yu Du; Xuejing Liu; Rui Feng; Yue Jia; Xiang Ren; Nuo Zhang; Lei Liu; Qin Wei; Huangxian Ju (Food Chemistry, 2023)

Estimation of in-season nitrogen requirement for drip-irrigated spring maize without or with straw incorporation using critical nitrogen dilution curve - Ru Guo; Rui Qian; Muhammad Asad Naseer; Fei Han; Peng Zhang; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Plant and Soil, 2023)

Featured immune characteristics of COVID-19 and systemic lupus erythematosus revealed by multidimensional integrated analyses - Xingwang Zhao; Mengjie Zhang; Yuying Jia; Wenying Liu; Shifei Li; Cuie Gao; Lian Zhang; Bing Ni; Zhihua Ruan; Rui Dong (Inflammation Research, 2023)

Agricultural intensification weakens soil multifunctionality by reducing fungal diversity - Rui Xue; Chong Wang; Lei Zhao; Jia Cao; Mengli Liu; Dong Zhang (Applied Soil Ecology, 2023)

Non-steady state fluctuations in water levels exacerbate long-term and seasonal degradation of water quality in river-connected lakes - Yingze Yin; Rui Xia; Yan Chen; Ruining Jia; Nixi Zhong; Chao Yan; Qiang Hu; Xiang Li; Hui Zhang (Water Research, 2023)

Effects of dietary supplementation of Anabaena sp. PCC7120 expressing VP28 protein on survival and histopathology after WSSV infection in Macrobrachium nipponense - Yupei Tong; Jia Yang; Li Wang; Xiaoping Chi; Chan Zhu; Rong Yin; Le Zhang; Yaru Li; Chunyan Zhao; Rui Jia (Fish & Shellfish Immunology, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Climate changes in the Hexi Corridor, western China over the past 13.3 ka - Yanzhen Li; Rui Zhang; Hao Long; Peng Cheng; David B. Kemp; Ze Zhang; Chunju Huang; Mengyang Hou; Yue Li; Shizhen Jia; Zhixiang Wang; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Astrochronology and sedimentary noise modeling of Pliensbachian (Early Jurassic) sea-level changes, Paris Basin, France - Rui Zhang; David B. Kemp; Nicolas Thibault; Mads E. Jelby; Mingsong Li; Chunju Huang; Yu Sui; Zhixiang Wang; Dongyang Liu; Shizhen Jia (Earth and Planetary Science Letters, 2023)

Spacecraft attitude fault-tolerant stabilization against loss of actuator Effectiveness: A novel iterative learning sliding mode approach - Qingxian Jia; Rui Ma; Chengxi Zhang; Renuganth Varatharajoo (Advances in Space Research, 2023)

Experimental study on low-damage performance of Sliding Hinge Joint - Junrong Liu; Rui Zhang; Zhenduo Yan; Jiang-Yue Xie; Kim Eng Chouery; Liang-Jiu Jia; Ping Xiang; Xianzhong Zhao; Shahab Ramhormozian; Rajesh P. Dhakal; G. Charles Clifton; Gregory A. MacRae (Soil Dynamics and Earthquake Engineering, 2023)

Insight into micropollutant abatement during ultraviolet light-emitting diode combined electrochemical process: Reaction mechanism, contributions of reactive species and degradation routes - Rui Hu; Sui-Qin Yang; Jia-Ying Li; Fengyi Sun; Zheng-Qian Liu; Jingjing Yang; Yu-Hong Cui; Beiping Zhang (Science of The Total Environment, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

A bionic mechanical foot with adaptive variable postures travelling on sand - Rui Zhang; Xumin Sun; Dianlei Han; Rui Zhang; Hua Zhang; Jia Ma; Lige Wen; Meng Zou (Journal of Terramechanics, 2023)

TRIM-containing 44 aggravates cardiac hypertrophy via TLR4/NOX4-induced ferroptosis - Leiming Wu; Meng Jia; Lili Xiao; Zheng Wang; Rui Yao; Yanzhou Zhang; Lu Gao (Journal of Molecular Medicine, 2023)

Short-term effect of apparent temperature on daily hospitalizations for osteoporotic fractures in Beijing, China: A retrospective observational study - Shuai Lu; Xuejiao Liu; Yanlin Niu; Feng Li; Maoqi Gong; Yejun Zha; Qingchen Chao; Bo Lu; Baichao Zhang; Ning Li; Jia Chen; Qiyong Liu; et al. (Science of The Total Environment, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Phosphorus – The main limiting factor in riverine ecosystems in China - Yan Chen; Jie Chen; Rui Xia; Wenpan Li; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2023)

Enhanced ultrasound-assisted pore-adjustable spherical imma-Fe3O4 catalytic-activated piezoelectric Fenton reaction for PDE-5i degradation - Zi-ang Jia; Qing-rui Zeng; Xun Zhang; Wei Feng (Journal of Environmental Chemical Engineering, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Morphological brain alterations in dialysis- and non-dialysis-dependent patients with chronic kidney disease - Huan Yu; Chaoyang Zhang; Yan Cai; Ning Wu; Xiuqin Jia; Jiaojiao Wu; Feng Shi; Rui Hua; Qi Yang (Metabolic Brain Disease, 2023)

Never in mitosis gene A-related kinase-6 deficiency deteriorates diabetic cardiomyopathy via regulating heat shock protein 72 - Shuangyin Shao; Lili Xiao; Meng Jia; Chuyang Zhang; Guojun Zhao; Rui Yao; Xiaofang Wang; Lu Gao (Journal of Molecular Medicine, 2023)

Understanding the Origin and Evolution of Tea (Camellia sinensis [L.]): Genomic Advances in Tea - Zai-Bao Zhang; Tao Xiong; Jia-Hui Chen; Fan Ye; Jia-Jia Cao; Yu-Rui Chen; Zi-Wei Zhao; Tian Luo (Journal of Molecular Evolution, 2023)

An improved light use efficiency model by considering canopy nitrogen concentrations and multiple environmental factors - Helin Zhang; Jia Bai; Rui Sun; Yan Wang; Zhiqiang Xiao; Bowen Song (Agricultural and Forest Meteorology, 2023)

Study on non-point source pollution characteristics under different spatial scales: a case study of Hanjiang River Basin, China - Ya-jiao Li; Jia-ping Wang; Zi-hang Zhang; Gai-rui Hao; Ya-fang Li; Jia-ke Li (Environmental Science and Pollution Research, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Circ_0021573 acts as a competing endogenous RNA to promote the malignant phenotypes of human ovarian cancer cells - Lifang Liu; Bingkai Han; Lixia Liu; Hongying Cui; Hao Liu; Rui Jia; Xiaoyan Zhang; Xiaoxiao Lu (Reproductive Biology, 2023)

Iron-based nanomaterials reduce cadmium toxicity in rice (Oryza sativa L.) by modulating phytohormones, phytochelatin, cadmium transport genes and iron plaque formation - Pingfan Zhou; Peng Zhang; Mengke He; Yu Cao; Muhammad Adeel; Noman Shakoor; Yaqi Jiang; Weichen Zhao; Yuanbo Li; Mingshu Li; Imran Azeem; Like Jia; et al. (Environmental Pollution, 2023)

Kidney Mesenchymal stem cells alleviate cisplatin-induced kidney injury and apoptosis in rats - Rui-ning Liang; De-qi Yan; Xing-ping Zhang; Xu Chen; Wen-hui Zhang; Hong-lin Jia (Tissue and Cell, 2023)

A national-scale distribution of organochlorine pesticides (OCPs) in cropland soils and major types of food crops in China: Co-occurrence and associated risks - Lu Chen; YongZhong Qian; Qi Jia; Rui Weng; Xinglian Zhang; Yun Li; Jing Qiu (Science of The Total Environment, 2023)

Sodium hydrosulfide alleviates aluminum toxicity in Brassica napus through maintaining H2S, ROS homeostasis and enhancing aluminum exclusion - Yan Yu; Jia Dong; Rui Li; Xue Zhao; Zonghe Zhu; Fugui Zhang; Kejin Zhou; Xianyong Lin (Science of The Total Environment, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Ameliorating C and N balance without loss of productivity by applying mulching measures in rainfed areas - Zihan Liu; Bingfan Wang; Zhaoyang Li; Chenxu Zhao; Rui Qian; Fangyuan Huang; Peng Zhang; Hui Li; ZhiKuan Jia (Agriculture, Ecosystems & Environment, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

New insights into the regulation mechanism of red claw crayfish (Cherax quadricarinatus) hepatopancreas under air exposure using transcriptome analysis - Yao-Peng Lu; Pei-Hua Zheng; Xiu-Xia Zhang; Jun-Tao Li; Ze-Long Zhang; Jia-Rui Xu; Yong-Qi Meng; Jia-Jun Li; Jian-An Xian; An-Li Wang (Fish & Shellfish Immunology, 2023)

Spatial distribution and quantitative source identification of nutrients and beneficial elements in the soil of a typical suburban area, Beijing - Qin-Rui Zhang; Sheng-Qiang Zhang; Yong Huang; Huan Li; Yan-Hui Jia; Jun Li; Guo-Li Yuan (Environmental Monitoring and Assessment, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Interactive Effects of Maize Straw-Derived Biochar and N Fertilization on Soil Bulk Density and Porosity, Maize Productivity and Nitrogen Use Efficiency in Arid Areas - Ru Guo; Rui Qian; Ling Yang; Abdul Khaliq; Fei Han; Sadam Hussain; Peng Zhang; Tie Cai; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Journal of Soil Science and Plant Nutrition, 2022)

Nitrogen occurrence forms and bacterial community in sediment influenced by Bellamya purificata bioturbation - Yiyun Zhang; Yiran Hou; Rui Jia; Bing Li; Jian Zhu; Xianping Ge (Frontiers in Marine Science, 2022)
Endogenous water pollution and excessive nitrogen in ponds have always been prominent problems threatening aquaculture. To solve this problem, a 70-day indoor simulation experiment was conducted. The snail Bellamya purificata was stocked at four different densities: 0, 15, 30, and 60 individuals/tank, represented as CON (control), LD (low density), MD (medium density), and HD (high density), respectively, to investigate the effects of B. purificata on the nitrogen occurrence forms and bacterial communities in the sediment. At the end of the experiment, the nitrate concentration was significantly higher, while the total nitrogen content was significantly lower in the MD group than in the other three groups. Ammonia monooxygenase activity was significantly lower in the CON group than in the other three groups, and hydroxylamine oxidase activity was significantly higher in the HD group than in the other three groups. The CON and MD groups showed the highest and lowest values in nitrate reductase activity, respectively. The hydroxylamine reductase activity decreased significantly with increasing density. Through 16S ribosomal RNA (rRNA) high-throughput sequencing, significantly affected bacterial communities by B. purificata were found. Alpha diversity results showed that, a significantly lower Shannon index was observed in the MD group than in the other three groups. The LD and MD groups showed the highest and lowest Chao1 index values, respectively. Phyla Nitrospinae and family Nitrosomonadaceae were significantly enriched in the HD and MD groups, respectively. Redundancy analysis (RDA) indicated a significant correlation between differential bacterial taxa and TN content. Predicted functional analysis based on FAPROTAX (Functional annotation of prokaryotic taxa) database showed that functional groups aerobic ammonia oxidation and aerobic nitrite oxidation were significantly enriched in the MD group. Overall, B. purificata significantly altered the bacterial community composition, increased hydroxylamine oxidase and ammonia monooxygenase activities, enhanced the bacterial nitrification process, and promoted the transformation of total nitrogen to nitrate. Moreover, B. purificata stocked at 30 and 60 individuals/tank appeared to have a significant promotion effect on the bacterial community and nitrogen occurrence forms in the sediment. Hence, co-culturing B. purificata may be a feasible and effective ecological restoration method to alleviate excess nitrogen and reduce water eutrophication.

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

Pyroptosis participates in PM2.5-induced air–blood barrier dysfunction - Ruxue Jia; Min Wei; Xiao Zhang; Rui Du; Wenping Sun; Lili Wang; Laiyu Song (Environmental Science and Pollution Research, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Regulation of Social Memory by Lateral Entorhinal Cortical Projection to Dorsal Hippocampal CA2 - Rui Dang; Yu Zhou; Yue Zhang; Die Liu; Miao Wu; An Liu; Zhengping Jia; Wei Xie (Neuroscience Bulletin, 2022)

Microseismic signal denoising by combining variational mode decomposition with permutation entropy - Zhang Xing-Li; Cao Lian-Yue; Chen Yan; Jia Rui-Sheng; Lu Xin-Ming (Applied Geophysics, 2022)

Transcriptome Analysis Reveals Molecular Mechanisms Underlying Methyl Jasmonate-mediated Biosynthesis of Protopanaxadiol-type Saponins in Panax notoginseng Leaves - Ying Li; Yuan Lin; Bing Jia; Geng Chen; Huineng Shi; Rui Xu; Xuejiao Li; Junrong Tang; Qingyan Tang; Guanghui Zhang; Jianli Yang; Wei Fan; et al. (Journal of Plant Biology, 2022)

Four new indole alkaloids from the roots of Isatis tinctoria - Dongdong Zhang; Yu Sun; Yanhong Shi; Ximin Wu; Qi Jia; Kaixian Chen; Yiming Li; Rui Wang (Natural Product Research, 2022)

Three-dimensional numerical simulation of geothermal field in space—wavenumber domain - Dai Shi-Kun; Jia Jin-Rong; Qiang Jian-Ke; Chen Qing-Rui; Ling Jia-Xuan; Zhang Ying (Applied Geophysics, 2021)

Heavy metal pollution from copper smelting during the Shang Dynasty at the Laoniupo site in the Bahe River valley, Guanzhong Basin, China - Menglei Wu; Yana Jia; Yuzhu Zhang; Rui Wen; Jiahua Guo; Ninglian Wang; Wanqing Liu; Haijun Qiu; Haoyu Wang; Yiheng Xian; Chun Yu; Ting Yang (Journal of Geographical Sciences, 2021)

A high-resolution timescale for the Miocene Shanwang diatomaceous shale lagerstätte (China): development of Wavelet Scale Series Analysis for cyclostratigraphy - Jifeng Yu; Xinlong Pang; Wenzhao Fu; Jason Hilton; Mingmei Liang; Zongkai Jiang; Xiuli Zhao; Wenyan Qiao; Suo Shi; Diandong Zhang; Huitao Cao; Haibo Jia; et al. (Geosciences Journal, 2021)

Genetic control of Fusarium head blight resistance in two Yangmai 158-derived recombinant inbred line populations - Haisheng Yan; Guoqiang Li; Jinxing Shi; ShunShun Tian; Xiaoqiu Zhang; Rui Cheng; Xin Wang; Yang Yuan; Shouyang Cao; Jiyang Zhou; Zhongxin Kong; Haiyan Jia; et al. (Theoretical and Applied Genetics, 2021)

Numerical modeling of 3D DC resistivity method in the mixed space-wavenumber domain - Shi-Kun Dai; Jia-Xuan Ling; Qing-Rui Chen; Kun Li; Qian-Jiang Zhang; Dong-Dong Zhao; Ying Zhang (Applied Geophysics, 2021)

Systematic analysis of differentially expressed ZmMYB genes related to drought stress in maize - Peng-Yu Zhang; Xiao Qiu; Jia-Xu Fu; Guo-Rui Wang; Li Wei; Tong-Chao Wang (Physiology and Molecular Biology of Plants, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Research on fault recognition method combining 3D Res-UNet and knowledge distillation - Jing Wang; Jun-Hua Zhang; Jia-Liang Zhang; Feng-Ming Lu; Rui-Gang Meng; Zuoqian Wang (Applied Geophysics, 2021)

Integrated analysis of miRNA and mRNA transcriptomic reveals antler growth regulatory network - Boyin Jia; Linlin Zhang; Yifan Zhang; Chenxia Ge; Fuhe Yang; Rui Du; Hengxing Ba (Molecular Genetics and Genomics, 2021)

Herbidospora solisilvae sp. nov., a novel cellulose-degrading actinobacterium isolated from forest soil - Mingying Yu; Rui Zhou; Jingjing Li; Liyuan Han; Han Wang; Siyu Zhang; Junwei Zhao; Xiangjing Wang; Jia Song; Wensheng Xiang (Antonie van Leeuwenhoek, 2021)

Rescue effects of Se-enriched rice on physiological and biochemical characteristics in cadmium poisoning mice - Yang Su; Ling Li; Muhammad Umer Farooq; Xin Huang; Tengda Zheng; Yu Jie Zhang; Hla Hla Ei; Faiz Hussain Panhwar; Zhichen Tang; Rui Zeng; Yuanke Liang; Xiaoying Ye; et al. (Environmental Science and Pollution Research, 2021)

Selective regulation in ribosome biogenesis and protein production for efficient viral translation - Hui-Jun Dong; Rui Zhang; Yu Kuang; Xiao-Jia Wang (Archives of Microbiology, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Dynamic Response of Phragmites australis and Suaeda salsa to Climate Change in the Liaohe Delta Wetland - Yushu Zhang; Wenying Yu; Ruipeng Ji; Yijun Zhao; Rui Feng; Qingyu Jia; Jinwen Wu (Journal of Meteorological Research, 2021)

The geological characteristics of the large- and medium-sized gas fields in the South China Sea - Gongcheng Zhang; Dongdong Wang; Lei Lan; Shixiang Liu; Long Su; Long Wang; Wu Tang; Jia Guo; Rui Sun (Acta Oceanologica Sinica, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Indole alkaloid glycosides from Isatis tinctoria roots - Dongdong Zhang; Kang Du; Yitian Zhao; Songshan Shi; Yingchun Wu; Qi Jia; Kaixian Chen; Yiming Li; Rui Wang (Natural Product Research, 2021)

Comparative transcriptomic and metabolomic analyses of carotenoid biosynthesis reveal the basis of white petal color in Brassica napus - Ledong Jia; Junsheng Wang; Rui Wang; Mouzheng Duan; Cailin Qiao; Xue Chen; Guoqiang Ma; Xintong Zhou; Meichen Zhu; Fuyu Jing; Shengsen Zhang; Cunmin Qu; et al. (Planta, 2021)
Main conclusion The molecular mechanism underlying white petal color in Brassica napus was revealed by transcriptomic and metabolomic analyses. Abstract Rapeseed ( Brassica napus L.) is one of the most important oilseed crops worldwide, but the mechanisms underlying flower color in this crop are known less. Here, we performed metabolomic and transcriptomic analyses of the yellow-flowered rapeseed cultivar ‘Zhongshuang 11’ (ZS11) and the white-flowered inbred line ‘White Petal’ (WP). The total carotenoid contents were 1.778-fold and 1.969-fold higher in ZS11 vs. WP petals at stages S2 and S4, respectively. Our findings suggest that white petal color in WP flowers is primarily due to decreased lutein and zeaxanthin contents. Transcriptome analysis revealed 10,116 differentially expressed genes with a fourfold or greater change in expression ( P -value less than 0.001) in WP vs. ZS11 petals, including 1,209 genes that were differentially expressed at four different stages and 20 genes in the carotenoid metabolism pathway. BnNCED4b , encoding a protein involved in carotenoid degradation, was expressed at abnormally high levels in WP petals, suggesting it might play a key role in white petal formation. The results of qRT-PCR were consistent with the transcriptome data. The results of this study provide important insights into the molecular mechanisms of the carotenoid metabolic pathway in rapeseed petals, and the candidate genes identified in this study provide a resource for the creation of new B. napus germplasms with different petal colors.

New potential strains for controlling Spodoptera frugiperda in China: Cordyceps cateniannulata and Metarhizium rileyi - Ye-Ming Zhou; Wen Xie; Jia-Qin Ye; Tao Zhang; Ding-Yin Li; Jun-Rui Zhi; Xiao Zou (BioControl, 2020)

Quantitative assessment of non-point source pollution load of PN/PP based on RUSLE model: a case study in Beiluo River Basin in China - Gai-rui Hao; Jia-ke Li; Shu Li; Kang-bin Li; Zi-hang Zhang; Huai-en Li (Environmental Science and Pollution Research, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Dissecting the Potential of Selenoproteins Extracted from Selenium-Enriched Rice on Physiological, Biochemical and Anti-Ageing Effects In Vivo - Rui Zeng; Muhammad Umer Farooq; Guo Zhang; Zhichen Tang; Tengda Zheng; Yang Su; Sajad Hussain; Yuanke Liang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Biological Trace Element Research, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Impact of selenium, zinc and their interaction on key enzymes, grain yield, selenium, zinc concentrations, and seedling vigor of biofortified rice - Hla Hla Ei; Tengda Zheng; Muhammad Umer Farooq; Rui Zeng; Yang Su; Yujie Zhang; Yuanke Liang; Zhichen Tang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Environmental Science and Pollution Research, 2020)

Comparative study on the bioaccumulation of lead, cadmium and nickel and their toxic effects on the growth and enzyme defence strategies of a heavy metal accumulator, Hydrilla verticillata (L.f.) Royle - Hong Zhang; Ling-Lei Zhang; Jia Li; Min Chen; Rui-Dong An (Environmental Science and Pollution Research, 2020)

Hand, foot, and mouth disease in Changsha City, China, 2009–2017: a new method to analyse the epidemiological characteristics of the disease - Dong Yang; Ruchun Liu; Lan Ye; Qingqing Hu; Jia Rui; Yinzhu Zhou; Heng Zhang; Xixing Zhang; Benhua Zhao; Tianmu Chen (Infectious Diseases, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Molecular mapping of the gene(s) conferring resistance to Soybean mosaic virus and Bean common mosaic virus in the soybean cultivar Raiden - Mian Wu; Ying-Na Liu; Cong Zhang; Xue-Ting Liu; Cheng-Chen Liu; Rui Guo; Ke-Xin Niu; An-Qi Zhu; Jia-Yin Yang; Jian-Qun Chen; Bin Wang (Theoretical and Applied Genetics, 2019)

Synthesis and antitumor evaluation of novel fused heterocyclic 1,2,4-triazolo[3,4-b]-1,3,4-thiadiazole derivatives - Xiao-Jia Liu; Hai-Ying Liu; Hai-Xin Wang; Yan-Ping Shi; Rui Tang; Shuai Zhang; Bao-Quan Chen (Medicinal Chemistry Research, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Alterations in transcriptome and antioxidant activity of naturally aged mice exposed to selenium-rich rice - Rui Zeng; Yuanke Liang; Muhammad Umer Farooq; Yujie Zhang; Hla Hla Ei; Zhichen Tang; Tengda Zheng; Yang Su; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Environmental Science and Pollution Research, 2019)

Study of the sedimentation and self-weight consolidation behavior of seafloor sediments using a radioisotope densitometer - Rui Jia; Huayang Lei; Wenjun Zhang; Takenori Hino (Marine Georesources & Geotechnology, 2019)

Genomic characterization and pathogenicity of porcine deltacoronavirus strain CHN-HG-2017 from China - Meng-Jia Zhang; De-Jian Liu; Xiao-Li Liu; Xing-Yi Ge; Anan Jongkaewwattana; Qi-Gai He; Rui Luo (Archives of Virology, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Energy-Based Brittleness Index and Acoustic Emission Characteristics of Anisotropic Coal Under Triaxial Stress Condition - Jun Zhang; Chi Ai; Yu-wei Li; Ming-guang Che; Rui Gao; Jia Zeng (Rock Mechanics and Rock Engineering, 2018)

Ferroptosis, a Recent Defined Form of Critical Cell Death in Neurological Disorders - Jia-rui Wu; Qing-zhang Tuo; Peng Lei (Journal of Molecular Neuroscience, 2018)

Fast 3D forward modeling of the magnetic field and gradient tensor on an undulated surface - Kun Li; Long-Wei Chen; Qing-Rui Chen; Shi-Kun Dai; Qian-Jiang Zhang; Dong-Dong Zhao; Jia-Xuan Ling (Applied Geophysics, 2018)

Characterization of clinical features and outcome for human-to-human transmitted severe fever with thrombocytopenia syndrome - Bei Jia; Weihua Wu; Rui Huang; Guiyang Wang; Peixin Song; Yang Li; Yong Liu; Yali Xiong; Xiaomin Yan; Yingying Hao; Juan Xia; Zhaoping Zhang; et al. (Infectious Diseases, 2018)

Ancylomarina psychrotolerans sp. nov., isolated from sediments of Fildes Peninsula and emended the description of genus Ancylomarina - Chao Jia; Hong-chang Cui; Yan-qiong Han; Tian-yu Fu; Rui Du; Xiao-lei Wang; Xiao-chong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2018)

Least squares reverse-time migration in the pseudodepth domain and reservoir exploration - Xiao-Dong Sun; Yan-Rui Jia; Min Zhang; Qing-Yang Li; Zhen-Chun Li (Applied Geophysics, 2018)

Identification of blasting vibration and coal-rock fracturing microseismic signals - Xing-Li Zhang; Rui-Sheng Jia; Xin-Ming Lu; Yan-Jun Peng; Wei-Dong Zhao (Applied Geophysics, 2018)

Nature and origin of Triassic igneous activity in the Western Qinling Orogen: the Wenquan composite pluton example - Kun-Feng Qiu; Hao-Cheng Yu; Zong-Yang Gou; Zhi-Lu Liang; Jia-Lin Zhang; Rui Zhu (International Geology Review, 2018)

A Fluorescent Sensor of 3-Aminobenzeneboronic Acid Functionalized Hydrothermal Carbon Spheres for Facility Detection of L-tryptophan - Rui Zhang; Li-Xia Wang; Yun-Di Zhang; Chun-Hua Ge; Jia-Ping Wang; Ying Zhang; Xiang-Dong Zhang (Journal of Fluorescence, 2018)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Protective effect of Ganoderma lucidum polysaccharide against carbon tetrachloride-induced hepatic damage in precision-cut carp liver slices - Yingjuan Liu; Chunyun Zhang; Jinliang Du; Rui Jia; Liping Cao; Galina Jeney; Hiroki Teraoka; Pao Xu; Guojun Yin (Fish Physiology and Biochemistry, 2017)

Apigenin attenuates streptozotocin-induced pancreatic β cell damage by its protective effects on cellular antioxidant defense - Ning Wang; Wen Jing Yi; Lu Tan; Jia Hui Zhang; Jiamin Xu; Yi Chen; Mengting Qin; Shuang Yu; Jing Guan; Rui Zhang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Intelligent diagnosis of jaundice with dynamic uncertain causality graph model - Shao-rui Hao; Shi-chao Geng; Lin-xiao Fan; Jia-jia Chen; Qin Zhang; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2017)

Does residual H2O2 result in inhibitory effect on enhanced anaerobic digestion of sludge pretreated by microwave-H2O2 pretreatment process? - Jibao Liu; Ruilai Jia; Yawei Wang; Yuansong Wei; Junya Zhang; Rui Wang; Xing Cai (Environmental Science and Pollution Research, 2017)

Assessing the vulnerability of changing coasts, Hainan Island, China - Yaping Wang; Benwei Shi; Liang Zhang; Jianjun Jia; Xiaomin Xia; Liang Zhou; Rui Yu; Yang Yang; Jianhua Gao (Acta Oceanologica Sinica, 2017)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Erythropoietin Attenuates the Memory Deficits in Aging Rats by Rescuing the Oxidative Stress and Inflammation and Promoting BDNF Releasing - Zhankui Jia; Rui Xue; Shengli Ma; Jingjing Xu; Si Guo; Songchao Li; Erwei Zhang; Jun Wang; Jinjian Yang (Molecular Neurobiology, 2016)

The Roles of Genes in the Neuronal Migration and Neurite Outgrowth Network in Developmental Dyslexia: Single- and Multiple-Risk Genetic Variants - Shanshan Shao; Rui Kong; Li Zou; Rong Zhong; Jiao Lou; Jie Zhou; Shengnan Guo; Jia Wang; Xiaohui Zhang; Jiajia Zhang; Ranran Song (Molecular Neurobiology, 2016)

Dust aerosol properties and radiative forcing observed in spring during 2001–2014 over urban Beijing, China - Xingna Yu; Rui Lü; K. Raghavendra Kumar; Jia Ma; Qiuju Zhang; Yilun Jiang; Na Kang; Suying Yang; Jing Wang; Mei Li (Environmental Science and Pollution Research, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Phylogenetic analysis of Leymus (Poaceae: Triticeae) based on Random Amplified Polymorphic DNA - Yang-Yi Li; Ying-Xia Lei; Guan-Hui Chai; Gang Gao; Jia-Bin Deng; Yan Zhang; Shan-Shan Tong; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Rui-Wu Yang (Biologia, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

ZmDBF3, a Novel Transcription Factor from Maize (Zea mays L.), Is Involved in Multiple Abiotic Stress Tolerance - Wei Zhou; Cheng-Guo Jia; Xian Wu; Rui-Xue Hu; Gang Yu; Xiang-Hui Zhang; Jin-Liang Liu; Hong-Yu Pan (Plant Molecular Biology Reporter, 2016)

Binariimonas pacifica gen. nov., sp. nov., a Novel Marine Bacterium of Family Sphingomonadaceae Isolated from East Pacific Ocean Surface Seawater - Zhao Zhao; Jia Sun; Rui Zhang; Nianzhi Jiao (Current Microbiology, 2015)

Molecular cloning and characterization of caffeic acid 3-O-methyltransferase from the rhizome of Ligusticum chuanxiong - Juan-Juan Li; Gan Zhang; Ji-hua Yu; Yang-yang Li; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2015)

Predicting invasions of Wedelia trilobata (L.) Hitchc. with Maxent and GARP models - Zhong Qin; Jia-en Zhang; Antonio DiTommaso; Rui-long Wang; Rui-shan Wu (Journal of Plant Research, 2015)

Modified halloysite nanotubes and the alleviation of kidney damage induced by dietary zearalenone in swine - Zhiqiang Jia; Shutong Yin; Min Liu; Yuanyuan Zhang; Rui Gao; Baoming Shi; Anshan Shan; Zhihui Chen (Food Additives & Contaminants: Part A, 2015)

Phylogenetic relationships among Elymus and related diploid genera (Triticeae: Poaceae) based on nuclear rDNA ITS sequences - Gang Gao; Jia-bin Deng; Xue-mei Gou; Qian Wang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2015)

An overview of passive and active dust detection methods using satellite measurements - Bin Chen; Peng Zhang; Beidou Zhang; Rui Jia; Zhijuan Zhang; Tianhe Wang; Tian Zhou (Journal of Meteorological Research, 2014)

Genomewide identification and expression analysis of the ARF gene family in apple - XIAO-CUI LUO; MEI-HONG SUN; RUI-RUI XU; HUAI-RUI SHU; JIA-WEI WANG; SHI-ZHONG ZHANG (Journal of Genetics, 2014)

PAHs in PM2.5 in Zhengzhou: concentration, carcinogenic risk analysis, and source apportionment - Jia Wang; Ning Bo Geng; Yi Fei Xu; Wen Ding Zhang; Xiao Yan Tang; Rui Qin Zhang (Environmental Monitoring and Assessment, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Seohaeicola westpacificensis sp. nov., A Novel Member of Genera Seohaeicola Isolated from Deep West Pacific Sea Water - Shuhui Xian; Rui Zhang; Jia Sun; Yi Chen; Wenchao Deng; Shuhui Li; Nianzhi Jiao (Current Microbiology, 2014)

Pollen morphology and its phylogenetic implications in the genus Picea - Zi Rui Jia; Jun Hui Wang; Shou Gong Zhang (Plant Systematics and Evolution, 2014)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Development of an immunochromatographic strip test for the rapid detection of okadaic acid in shellfish sample - Leqin Hu; Junxiu Liu; Qing Wang; Yang Zhang; Rui Jia; Chuner Cai; Weining Wu; Steven-Feng Chen; Peimin He (Journal of Applied Phycology, 2013)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

Pelagibacterium nitratireducens sp.nov., A Marine Alphaproteobacterium Isolated from the East China Sea - Qipei Li; Yongle Xu; Keshao Liu; Lanlan Cai; Yingnan Fu; Jia Sun; Rui Zhang (Current Microbiology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Exogenous hydrogen sulfide attenuates diabetic myocardial injury through cardiac mitochondrial protection - Xin Zhong; Leihong Wang; Yuwen Wang; Shiyun Dong; Xiaoning Leng; Jing Jia; Yajun Zhao; Hulun Li; Xinying Zhang; Changqing Xu; Guangdong Yang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2012)

Microsporogenesis and development of the male gametophyte in Allium senescens L. (Liliaceae) in China - Jiao Zhang; Xiao-Rui Liu; Fei-Xiong Zhang; Jia-Xi Liu (Plant Systematics and Evolution, 2012)

ST13, a proliferation regulator, inhibits growth and migration of colorectal cancer cell lines - Rui Bai; Zhong Shi; Jia-wei Zhang; Dan Li; Yong-liang Zhu; Shu Zheng (Journal of Zhejiang University-SCIENCE B, 2012)

Genetic characterization of Aleutian mink disease viruses isolated in China - Yanwu Li; Juan Huang; Yun Jia; Yijun Du; Ping Jiang; Rui Zhang (Virus Genes, 2012)

Highly Selective and Sensitive Chemosensor for Hg2+ Based on the Naphthalimide Fluorophore - Rui Yang; Xiangfeng Guo; Wei Wang; Yu Zhang; Lihua Jia (Journal of Fluorescence, 2012)

Effects of a non-selective TRPC channel blocker, SKF-96365, on melittininduced spontaneous persistent nociception and inflammatory pain hypersensitivity - Jing Ding; Jia-Rui Zhang; Yan Wang; Chun-Li Li; Dan Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2012)

A New Piezochromic Fluorescence and Aggregation-Induced Emission Compound Containing Tetraphenylethylene and Triphenylamine Moieties with Morphology-alterable Property - Xie Zhou; Hai-yin Li; Zhen-guo Chi; Bing-jia Xu; Xi-qi Zhang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2012)

Synthesis and Characterization of Triphenylethylene Derivatives with Aggregation-Induced Emission Characteristics - Xiao-Fang Li; Zhen-Guo Chi; Bing-Jia Xu; Hai-Yin Li; Xi-Qi Zhang; Wei Zhou; Yi Zhang; Si-Wei Liu; Jia-Rui Xu (Journal of Fluorescence, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Pollen morphology of Hosta Tratt. in China and its taxonomic significance - Jia-Xi Liu; Chun-Hai Zhao; Xiao-Rui Liu; Yi-Zhen Xi; Yu-Long Zhang (Plant Systematics and Evolution, 2011)

The cardioprotective effect of fluvastatin on ischemic injury via down-regulation of toll-like receptor 4 - Jun Yang; Xiao-Dong Zhang; Jian Yang; Jia-Wang Ding; Zhao-Qi Liu; Shu-Guo Li; Rui Yang (Molecular Biology Reports, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Comparison of Responsive Behaviors of Two Cinnamic Acid Derivatives Containing Carbazolyl Triphenylethylene - Xi-qi Zhang; Zhen-guo Chi; Bing-jia Xu; Hai-yin Li; Wei Zhou; Xiao-fang Li; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Photocatalytic degradation of organic dyes by Er3+:YAlO3/TiO2 composite under solar light - Jun Wang; Yingpeng Xie; Zhaohong Zhang; Jia Li; Chengwu Li; Liquan Zhang; Zhiqiang Xing; Rui Xu; Xiangdong Zhang (Environmental Chemistry Letters, 2010)

NMDA receptor antagonist MK-801 reduces neuronal damage and preserves learning and memory in a rat model of traumatic brain injury - Rui-Zhang Han; Jin-Jia Hu; Yuan-Chi Weng; Ding-Feng Li; Yi Huang (Neuroscience Bulletin, 2009)

Genome-wide Comparisons of Gene Expression for Yield Heterosis in Maize - Bo Li; Deng-Feng Zhang; Guan-Qing Jia; Jing-Rui Dai; Shou-Cai Wang (Plant Molecular Biology Reporter, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Rapid Quantitative Detection of Vibrio parahaemolyticus in Seafood by MPN-PCR - Xiaoyan Luan; Jixiang Chen; Yu Liu; Yun Li; Juntao Jia; Rui Liu; Xiao-Hua Zhang (Current Microbiology, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

An experimental study of the mechanisms of freeze/thaw and wind erosion of ancient adobe buildings in northwest China - Jian-Jun Qu; Guo-Dong Cheng; Ke-Cun Zhang; Jia-Cheng Wang; Rui-Ping Zu; Hai-Yan Fang (Bulletin of Engineering Geology and the Environment, 2007)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)

The wheat TaGI1, involved in photoperiodic flowering, encodesan Arabidopsis GI ortholog - Xiang Yu Zhao; Mao Sen Liu; Jia Rui Li; Chun Mei Guan; Xian Sheng Zhang (Plant Molecular Biology, 2005)

Research progress of socio-economic water cycle in China - Jia Shao-feng; Wang Guo; Zhang Shi-feng; Yu Gui-rui; Wang Jin-xia; Xia Jun (Journal of Geographical Sciences, 2002)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)